Linking physicochemical properties to combustion performance: Effects of torrefaction and briquetting on sugarcane bagasse - Millos Julián Enrique Jinete Torres; Gabriel Alexandre Pio; Juan Pablo Arteaga Ramos; Yesid Javier Rueda Ordoñez; Juliana Esteves Fernandes Cieslinski; Carlos Manuel Romero Luna (Biomass and Bioenergy, 2027)

Supplementation of IVM media with equine follicular fluid of large follicles increases blastocyst yield in equine ICSI programs - Luciana Ribeiro Peixoto; Marcos Antônio Gonçalves; José Henrique Fortes Pontes; Perla Dagher Cassoli Fleury; Gustavo Pulzatto Merlini; Thiago Alexandre Robilotta de Oliveira; Victoria Martins Braghetto Barillari; Cláudia Barbosa Fernandes; José Buratini; Vilceu Bordignon; Felipe Perecin (Theriogenology, 2026)

Intraspecific variation in Bothrops neuwiedi snake venom: Influence of age and sex - Eduardo Oliveira Venancio de Lima; Juan David Gutiérrez Marín; Lídia Jorge Tasima; Caroline Serino-Silva; Jackson Gabriel Miyamoto; Alexandre Keiji Tashima; Kathleen Fernandes Grego; Anita Mitico Tanaka-Azevedo (Toxicon, 2026)

Wet-cold forest altitudinal shifts during the Pleistocene-Holocene in the Brazilian central mountain range (Serra do Espinhaço Meridional) - Ingrid Horák-Terra; Antonio Martínez Cortizas; Cynthia Fernandes Pinto da Luz; Kauê Fonseca; Katerine Escobar Torrez; Marie-Pierre Ledru; Fabrício da Silva Terra; Plínio Barbosa de Camargo; Alexandre Christófaro Silva; Pablo Vidal-Torrado; Olalla López-Costas (CATENA, 2026)

Integrated approaches to atmospheric radionuclide dispersion for emergency management at the Brazilian nuclear complex - Alexandre Soares dos Santos; Luiz Claudio Gomes Pimentel; Corbiniano Silva; Paulo Fernando Lavalle Heilbron Filho; Itamar Frederico Souza Gonçalves; Pryscila Jesus de Sousa; Anselmo de Souza Pontes; Filipe Fernandes de Carvalho Souza; Larissa de Freitas Ramos Jacinto; Mauricio Soares da Silva; José Francisco de Oliveira Júnior; Anel Hernández Garces; et al. (Meteorology and Atmospheric Physics, 2026)
This study evaluates the potential impacts of hypothetical nuclear accidents at the Almirante Álvaro Alberto Nuclear Power Plant (CNAAA), located in Angra dos Reis (RJ), in the southeastern region of Brazil, through the integration of advanced atmospheric modeling and Geographic Information Systems (GIS). The study area is characterized by complex environmental features, including mountainous terrain, remnants of the Atlantic Forest, coastal ecosystems, conservation units, and intense tourist activity. To simulate accidental release scenarios of iodine-131 (¹³¹I), the WRF/CALMET/CALPUFF modeling system was applied, incorporating high-resolution meteorological data and accounting for seasonal variability as well as topographic influences. The integration of WRF and CALMET for meteorological characterization, combined with CALPUFF dispersion simulations, provided realistic representations of the wind field, conferring confidence to the simulated dispersion patterns. A comprehensive radiological dose assessment was performed, including inhalation (short-term), external exposure to the plume (short-term), soil deposition (medium-term), and milk ingestion via the pasture → milk pathway (long-term), with comparison to the intervention levels of the IAEA (GSG-2) and CNEN (NE-1.04). The results indicate that, for children in the most impacted area, the total accumulated dose over 30 days exceeds 100 mSv, justifying the need for revision of the current Emergency Planning Zones (EPZs). The periods from November to March and from May to July present unfavorable dispersion conditions, associated with climatic instability and hydrological events. In summary, the methodological framework highlights the relevance of combining atmospheric modeling and geotechnological tools to strengthen nuclear safety and enhance emergency preparedness in coastal and densely populated regions.

Land-use impacts on a soil ecosystem services index in the Brazilian Atlantic Forest biome - Maria Cecília Vieira Totti; Sérgio Henrique Godinho Silva; Bruno Montoani Silva; Ricardo de Oliveira Bordonal; Fernanda Almeida Bócoli; Vanêssa Lopes de Faria; Adriana Marcela Silva-Olaya; Andrés Olaya Montes; Alexandre Uezu; Laury Cullen Junior; Vinícius Ferreira Fernandes; Junior Cesar Avanzi (Geoderma Regional, 2026)

Changes in the taxonomic, functional and phylogenetic diversity of fish assemblages on beaches with contrasting morphodynamic characteristics - Alexandre da Gama Fernandes Vieira-Júnior; Éden Hávila Lima Guedes; André Luiz Machado Pessanha (Estuarine, Coastal and Shelf Science, 2026)

Integrative cytogenetic and molecular analyses in Hypostomus sertanejo reveal the lowest diploid number in the genus (Siluriformes: Loricariidae) - Daniela Rodrigues; Ligia Carla Balini; Bárbara Scorsim; Cláudio Henrique Zawadzki; Alessandra Valéria de Oliveira; Marcos Otávio Ribeiro; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes; Eliane Papa Ambrosio-Albuquerque; Luciana Andreia Borin-Carvalho (Biologia, 2026)
Expanding integrative cytogenetic and molecular analyses is essential for understanding the evolutionary dynamics of chromosome number variation in fishes. This study presents the first cytogenetic characterization of Hypostomus sertanejo , an endemic species native to the semi-arid Jaguaribe River basin in Northeastern Brazil. Cytogenetic analysis revealed a diploid number of 2n = 52, which is the lowest documented for the genus, with a karyotype composed of 22m + 8sm + 16st + 6a and a fundamental number of 98. This value aligns with the ancestral diploid number suggested for the tribe Hypostomini. Fluorescence in situ hybridization identified a single 18S rDNA site coinciding with the nucleolar organizer region, while 5S rDNA was localized to an interstitial position on a unique chromosome pair. Molecular analysis based on COI gene confirmed the identity of H. sertanejo and its distinction from closely related species. These results reveal a distinctive evolutionary trajectory for H. sertanejo relative to other Hypostomus species and highlight the importance of integrating data to elucidate diversification patterns in endemic fish lineages.

Rotundedessa gen. n., a New Edessinae Genus with the Description of Two New Species from Argentina (Hemiptera: Pentatomidae) - María Cecilia Martínez; Freddy Burgos Gallardo; José Antonio Marin Fernandes; Luiz Alexandre Campos (Neotropical Entomology, 2026)
The Edessinae is a Neotropical subfamily of Pentatomidae comprising hundreds of species in 20 genera. The nominal genus Edessa Fabricius, 1803 includes most of this diversity with approximately 350 nominal species, and can be considered a “depot taxon.” Studying small groups of morphologically similar species is an efficient approach to deal with the taxonomic diversity in Edessa and has led to the description of several new genera. The viridula group comprises five species and is characterized by short metasternal processes, wrinkled ventrolateral areas, and pygophore with several unique features. Following the current standards in the taxonomy of Edessinae, we consider these characteristics distinctive enough to propose a new genus to the species included in the viridula group. The new genus is herein described and new combinations for the five species formerly placed in the viridula group are proposed. Additionally, two new species from Argentina are described, and a key to the species of the new genus is given.

Therapeutic potential of Syzygium cumini L. extract in treating anxiety in adult zebrafish (Danio rerio): Behavioral, toxicological, and molecular evidence involving the GABAergic and serotonergic pathways - Cássia Taiane Viana Moraes; Gabriel Martins de Araújo Sousa; Ariel Falanga de Oliveira; Igor de Codes Soares; Paula Ticiani Alves de Souza; Lucca Moura de Freitas; Mário Guilherme de Paula Sales; Vitória Isabele Gomes Ferreira; Paula Alexandre de Freitas; Saulo Chaves Magalhães; Katarine Ferreira da Silva; Luís Sérgio Fonteles Duarte; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Effect of the application of fermented milk and microbial inoculants on whole-plant corn silage during relocation - Lifranc Laurent; Alexandre Fernandes Perazzo; Samila Barbosa Lisboa; Shirlenne Ferreira Silva; Angelina Milka Veras da Costa; Andreza Maria Ribeiro da Cruz; Walyson Alves de Araújo; João Paulo Matos Pessoa; Maysa Callado Moura; Danillo Marte Pereira; Edson Mauro Santos; Ricardo Loiola Edvan (Animal Feed Science and Technology, 2026)

Structural abnormalities in erythrocytes and a potential denucleation process induced by metformin, compromising cell viability in specimens of Astyanax lacustris (Pisces, Characidae) - Luara Lupepsa; Pablo Américo Barbieri; Brennda Ribeiro Paupitz; Vanessa Oliveira Sales-Zampar; Helito Volpato; Fernanda Errero Porto Saparolli; Eliane Papa Ambrosio-Albuquerque; Carlos Alexandre Fernandes; Luciana Andreia Borin-Carvalho; Ana Luiza de Brito Portela-Castro (Environmental Science and Pollution Research, 2026)
Hematological studies in fish are sensitive indicators of physiological and pathological changes caused by aquatic pollution, including pharmaceutical contaminants. Among these pollutants, metformin is one of the most prevalent and has been associated with adverse effects on aquatic organisms. However, its impact on fish erythrocyte morphology remains poorly understood. This study evaluated the cyto- and genotoxic effects of metformin on erythrocytes of Astyanax lacustris through morphological analyses, membrane integrity assessment by flow cytometry, and DNA damage evaluation using comet assay. Fish were exposed to metformin concentrations of 50, 100, and 10,000 µg/L for 90 days. Exposure induced significant erythrocyte alterations, particularly at higher metformin concentrations, including membrane invaginations and ruptures, cytoplasmic vacuolization, nuclear abnormalities, DNA damage, peripheral nuclei, and formation of erythroplastids, suggesting denucleation process. Flow cytometry also revealed an increased proportion of non-viable cells. These findings suggest that metformin may significantly impair erythrocyte physiology and viability, potentially compromising the health of exposed fish.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Effects of encapsulated nitrate replacing urea on performance, rumen fermentation, and enteric methane emissions in grazing Nellore cattle from weaning to slaughter - Rodolfo M. Fernandes; Yury T. Granja-Salcedo; Leandro S. Sakamoto; Laura F. Prados; Alexandre Berndt; Rafael C. Araujo; Flávio D. Resende; Gustavo R. Siqueira (Science of The Total Environment, 2026)

Forest restoration enhances soil health in tropical agricultural landscapes assessed by soil management assessment framework (SMAF) across land uses and soil types - Vanêssa Lopes Faria; Helen Carla Santana Amorim; Maria Cecília Vieira Totti; Fernanda Almeida Bócoli; Junior Cesar Avanzi; Sérgio Henrique Godinho Silva; Alexandre Uezu; Amanda J. Ashworth; Gerson L. Drescher; Lara Mota Corinto; Samara Martins Barbosa; Vinícius Ferreira Fernandes; et al. (Geoderma Regional, 2026)

Effect of zinc oxide nanoparticle supplementation in Santa Inês ewes during the transition period - Willinton Hernan Pinchao Pinchao; Henrique de Brito Guedes; Carolina Rodriguez Jimenez; Gabriele Rossini Moreira; Murilo Antônio Fernandes; Bruna Gonçalves Santos Costa; Luciana Morita Katiki; Elisabete Aparecida de Nadai Fernandes; Mateus Oliveira Mena; César Cristiano Bassetto; Ana Cláudia Alexandre de Albuquerque; Alessandro Francisco Talamini do Amarante; et al. (Tropical Animal Health and Production, 2026)
Zinc oxide nanoparticles (N-ZnO) represent a promising alternative for zinc (Zn) supplementation, since their reduced size provides greater bioavailability and better integration into the body. Furthermore, this characteristic becomes particularly relevant during periods of increased metabolic stress, such as the transition phase. Thus, the objective was to evaluate the effects of N-ZnO supplementation in Santa Inês sheep during the peripartum period. Thirty-three ewes with an average body weight of 43.3 ± 2.05 kg were, distributed into three experimental groups: control group (CON), without supplementation, receiving only Cynodon spp. hay; and groups supplemented with 300 mg/animal/day of N-ZnO (40 nm) and zinc oxide microparticles (M-ZnO). The supplementation was administered orally in capsules daily from late pregnancy until weaning. The results showed no significant differences ( P > 0.05) in body weight, egg count per gram of feces (EPG), and in most of the hematological, biochemical, and immunological parameters evaluated. However, differences ( P < 0.05) were observed in monocyte counts and albumin levels, with higher means in the N-ZnO group, showing differences compared with the M-ZnO group, while the CON group maintained intermediate values. The N-ZnO group showed differences compared to the M-ZnO group, while the CON group maintained intermediate values. Regarding antioxidant activity, a significant effect ( P < 0.05) was observed on the enzymes Superoxidase dismutase (SOD), Glutathione peroxidase (GPx), Catalase (Cat), and on the total antioxidant status (ORAC) of the sheep supplemented with N-ZnO. It is concluded that N-ZnO supplementation improved the antioxidant response, with no signs of intoxication, using a dose of 300 mg during the period of greatest oxidative stress.

Predictive modeling of Rhopalosiphum padi population dynamics in time and space: host effects on management - Talison Roberto Maurer; Mateus Riva Donati; João Pedro Moretti; Jose Mauricio Cunha Fernandes; Alexandre Tagliari Lazzaretti; Roberto Wiest; Crislaine Sartori Suzana-Milan; Douglas Lau; Rafael Rieder (Journal of Plant Diseases and Protection, 2026)
The determination of biological parameters and the spatiotemporal dynamics of insect pests is essential for calibrating simulation models that enable the prediction of population growth and the establishment of warning systems for management actions. In this context, the objective of this study was to quantify variations in biological parameters due to the host (wheat cultivar) and their impacts on the accuracy of the ABISM (Agent-Based Insect Simulation Model). Since the rates of biological processes vary depending on the host plant, life-history parameters were obtained for two wheat cultivars (cv. TBIO Toruk and cv. BRS Belajoia) and compared to those simulated by ABISM. The pre-reproductive period was shorter, and longevity and the number of R. padi nymphs produced were higher in cv. BRS Belajoia compared to cv. TBIO Toruk. Differences were found between observed and ABISM-simulated data, depending on the cultivar, for the variables longevity ( $$p = 0.004793$$ ) and total fecundity ( $$p = 0.04443$$ ). These differences were expressed in spatial dynamics, with a greater number of plants colonized by R. padi in cv. BRS Belajoia. Differences between cultivars may be associated with anatomical traits, given that cv. BRS Belajoia lacks trichomes, unlike cv. TBIO Toruk. Therefore, there was an effect of cultivar and ambient temperature, and discrepancies between observed and simulated data only for cv. BRS Belajoia. The differences between cultivars, as well as in relation to the model, indicate, for better model accuracy, the use of cultivar-specific parameters considering insect–plant interactions is required.

Optimization of corneal preservation media with novel antifungal agents - Paula Reginatto; Giovanna de Jesus Agostinetto; Claudete Inês Locatelli; Felipe Silva Guareze; Angélica Rocha Joaquim; Maria Eduarda Krummenauer; Rúbia do Nascimento Fuentefria; Marilene Henning Vainstein; Diane Ruschel Marinho; Saulo Fernandes de Andrade; Alexandre Meneghello Fuentefria (Archives of Microbiology, 2026)
The performance of ophthalmic surgeries, particularly penetrating keratoplasty, is associated with an increased risk of ocular infections, especially fungal keratitis. In addition to infections such as post-surgical occlusions, microbial contamination of the donor’s tissue, predominantly fungal in nature, can also lead to the disposal of said tissue. The genus Fusarium , along with several species from the Candida genus, emerge as the primary fungal agents, displaying notable biofilm-forming abilities on surfaces. To address these issues, the addition of antifungals to preservation media vials has been explored, although conventional antifungal agents exhibit limitations. In light of this, compounds such derived from 8-hydroxyquinoline, clioquinol (CLQ) and PH151, emerge as promising alternatives. Hence, this study aimed to assess the efficacy of two derivatives of 8-hydroxyquinoline, both individually and in combination with antifungal agents, as additives in preservation media for human corneas intended for transplantation. Given the antifungal potential of CLQ and the combination voriconazole-amphotericin B-clioquinol, the ability to inhibit fungal growth and biofilm formation in human corneas preserved in Optisol-GS medium was investigated, as well as the endothelial viability of this tissue in the presence of these compounds. Among the tested antifungal agents, the combination of voriconazole, amphotericin B, and clioquinol stood out for its excellent antibiofilm action and potential to reduce the fungal load on the surface of the corneas, did not present endothelial toxicity. Thus, the results underscore the promising nature of this combination as a potential additive in hypothermic corneal preservation media, outlining a viable pathway to enhance corneal transplant efficacy.

Influence of coral reef morphology on wave climate and sea-level rise projections along a reef-protected beach in Northeast Brazil - Larissa Fernandes de Lavor; Maria Cecilia Silva Souza; Karina Massei; Alexandre dos Santos Souza; Valdir do Amaral Vaz Manso; Virgínio Henrique de Miranda Lopes Neumann; Pedro Costa Guedes Vianna; Christianne Maria da Silva Moura; Nadja Cecília de Freitas Silva; Richarde Marques da Silva; Rogério dos Santos Ferreira; Jefferson da Costa Silva; et al. (Regional Studies in Marine Science, 2026)

miRNA-mRNA integrative profiling in canine tubulopapillary mammary carcinoma - Nayra Cristina Herreira do Valle; Matheus Fujimura Soares; Natália Francisco Scaramele; Amanda de Oliveira Furlan; Maria Fernanda da Silva Lopes; Juliana de Souza Felix; Fernando Vissani Fernandes; Vinicius Aquiles Gomes Zamboni; Igor Luiz Salardani Senhorello; Alexandre Lima de Andrade; Flavia Lombardi Lopes (Research in Veterinary Science, 2026)

Food use, behavioral and cultural significance of the wood-boring mollusc Turu (Teredo sp.) in the Brazilian Amazon - Danilo Vitor Vilhena Batista; Larissa Aparecida Moreira de Castro; Adriana Fernandes de Barros; Caio Francisco Santana Farias; Ana Paula de Souza; Alexandre Vaz da Silva; Carolina Cerqueira Lima Dittrich; Emilly Monteiro Lopes; Elenice Martins Brasil; Marco Shizuo Owatari; José Luiz Pedreira Mouriño; Maurício Laterça Martins (Food and Humanity, 2026)

Ecotoxicological Assessment of Metal Pollution using Aquatic Organisms in Surface Sediments from a Tropical Urbanized Lagoon System - Matheus Teixeira; Ricardo Cesar; Denis Moledo de Souza Abessa; Ignacio Moreno-Garrido; Yan Fernandes; Katia Alexandre; Manuel Carneiro; Sofia Hart Rodes; João Vítor Castro; Camila Prieto; Adan Lino; Cláudio Parente; et al. (Estuaries and Coasts, 2026)
This study documents an ecotoxicological evaluation of bottom sediments ( n = 21) from a tropical lagoon complex performed in the Itaipu-Piratininga system (Rio de Janeiro State), an impacted urban tropical estuary. To achieve this purpose, three lines of evidence were adopted: sediment characterization, metal contamination and toxicity to tropical species (bioassays with mussels Perna perna , tanaids Kalliapseudes schubartii , amphipods Tiburonella viscana , and microalgae Cylindrotheca closterium) . The sediments from Piratininga lagoon were muddier and more organically enriched than those from Itaipu lagoon, once only the last one is influenced by an active connection with the ocean. Sediment texture and organic matter played a crucial role in metal distribution, but contaminated river mouths and the canal connecting the lagoons presented elevated Zn, Cu, Cd, Cr, Ni and P concentrations, which seem to be linked to domestic sewage discharges and other anthropic wastes. In addition, Pb and Mo hot spots were associated with an embayment area in Piratininga lagoon. Mussel embryo-larval development was 100% abnormal for all the samples. Although almost all the samples were toxic to tanaids and amphipods, tanaid mortality (mean ± SD = 76.4 ± 23.6%) was significantly higher than amphipod one (56.3 ± 20.4%). Inhibition of algae reproduction was the endpoint of lower concern (31.1 ± 26.5%). The toxicity was especially higher in river mouths and in the canal that connects the lagoons, being significantly correlated with sewage-related pollutants (Zn, Cu and P). Finally, although spatial variability of the toxicity has been explained by metal pollution along the lagoons, other toxicants should also be considered as stressors.

Metacommunity Structure, Species Richness and Species Composition of Reef Fish Trophic Guilds Along an Extensive Latitudinal Gradient in the Tropics - Alexandre da Gama Fernandes Vieira Júnior; Steven J. Presley; Michael R. Willig; Carlos Werner Hackradt; Fabiana Cézar Félix‐Hackradt; João Lucas Leão Feitosa (Journal of Biogeography, 2026)
Aim Our goals were (1) to identify the metacommunity structure of the reef fish fauna as well as the structure of its constituent trophic guilds (invertivores, generalist carnivores, omnivores, herbivores, planktivores and piscivores); (2) to evaluate the extent to which metacommunity compartmentalization is associated with biogeographic phenomena (isolation by distance, habitat filtering, estuarine plumes): and (3) to identify whether the latent environmental gradient that structures the metacommunity is related to latitude. Location Coral reefs of the Brazilian Biogeographic Province (BBP). Time Period 1998–2022. Major Taxa Studied Reef fish. Methods We categorized the BBP into biogeographic regions defined by spatio‐environmental characteristics and analysed the distribution of fish species in 150 sites that included a variety of reef types (abiogenic, biogenic and island‐associated reefs). For the entire fauna, and for each of its constituent trophic guilds, we ordinated their site‐by‐species incidence matrix using reciprocal averaging. Thereafter, we evaluated coherence, species turnover and species boundary clumping to determine the structure of each metacommunity. To quantify whether latitudinal variation affects the latent environmental gradient that structures the metacommunity, we performed Spearman rank correlation analyses of site scores from reciprocal averaging. In addition, we used a suite of nested general additive models and hierarchical a priori analyses to explore the extent to which compositional differences between biogeographic regions contributed to the compartmentalization of metacommunities. Results In general, the metacommunity structure of the reef fish fauna is moulded by latitudinal correlates and exhibits compartmentalization (Clementsian and quasi‐Clementsian structure) with compositionally distinct compartments arising because of isolation by distance (island vs. continental reefs), habitat filtering (abiogenic vs. biogenic reefs), or the influence of estuarine plumes associated with the mouths of large rivers. Nonetheless, the number and identity of compartments differed among trophic guilds. Island and continental reefs were compositionally distinct for the entire fish fauna, as well as for invertivores and omnivores. Biogenic and abiogenic reefs were compositionally distinct for omnivores, herbivores and piscivores. Northern and eastern biogenic reefs were compositionally distinct for invertivores, omnivores and piscivores. Main Conclusions Degree of isolation (island versus continental reefs) and dispersal barriers (habitat types and estuarine plumes) likely interact to affect the pervasive compartmentalization of marine fish metacommunities in the BBP. The extent to which they operate is guild‐specific, suggesting that the nature of compartmentalization in the fauna is a composite of contributions by different guilds, especially those with high species richness.

Electroretinographic measures and their correlation with retinal vascular calibers in bitches with pyometra-induced systemic inflammatory response syndrome - Fábio Dumit Pizzinatto; Alexandre Pinto Ribeiro; Bianca Eidt Rodrigues; Emilio Fernandes Rodrigues Junior (Research in Veterinary Science, 2026)

Sustainable oxygen-functionalized graphitic carbons from agro-waste: Influence of biomass source on atenolol removal - Nathália Magno Galdino; Mayara Bitencourt Leão; Rodrigo Morawski; Alexandre G. Brolo; Andreia Neves Fernandes; Jacqueline Ferreira Leite Santos (Journal of Environmental Chemical Engineering, 2026)

Genetic structure of the shea tree (Vitellaria paradoxa C.F. Gaertn.) population and fatty acid-based selection of elite genotypes in Benin - Guillaume J. Bodjrenou; Matice Gbètoho; Fernande Honfo; Cyril J. F. Kahn; M. Eric Schranz; Paul Césaire Gnanglè; Alain Hehn; Alexandre Olry; Enoch G. Achigan-Dako (Physiology and Molecular Biology of Plants, 2026)

Effect of planting mixed and facilitating species on the regenerating community - Raimundo Gomes da Silva Junior; Alessandro Camargo Ângelo; Nelson Luiz Cosmo; Roman Carlos Rios; Lorena de Souza Tavares Bressiani; Alexandre Dal Forno Mastella; Chaiane Rodrigues Schneider; Karen Koch Fernandes de Souza; Ingo Isernhagen; Elivane Salete Capellesso; Emi Silva Oliveira (Brazilian Journal of Botany, 2026)
Ecological restoration is essential to recovering degraded ecosystems and reestablishing fundamental environmental processes such as stability, succession, and resilience. This study evaluated whether the mixed planting of eight native forest species and the facilitator species Baccharis dracunculifolia influences Floristic community composition and diversity indices, phytosociological parameters, patterns of species community composition between treatments, and the effect of overgrowth and light on natural regeneration in areas undergoing ecological restoration. The experiment was conducted at the Canguiri Farm Experimental Station, Paraná, Brazil, using a randomized block design with two treatments and four replicates. Plots of 432 m 2 were monitored four and five years after planting (2023–2024). We do not find differences between treatments regarding Floristic composition. The results indicated that both treatments mixed planting (T1) and planting with facilitating species (T2) showed an increase in floristic richness, diversity, and abundance between 2023 and 2024, with T1 maintaining slightly higher values of diversity (Shannon index) and evenness (Pielou index) over time. Baccharis semiserrata and B. dracunculifolia stood out in the phytosociological parameters, being dominant in treatments and years. The PCoA analysis revealed significantly different floristic compositions between treatments in both years. Finally, a negative effect of light was observed on diversity and evenness in T1 in 2024 and on diversity and richness in T2 in 2023.

L-asparaginase by filamentous fungi and yeasts from lichens and soils across maritime Antarctic islands - Averlane Vieira da Silva; Bárbara Emanuelle Fernandes Ferro; Vanessa Daiany Vieira Medeiros; Valdilene Canazart dos Santos; Maria Nicolle Pereira da Silva; Cledna Kaline dos Santos Duarte; Aline Cavalcanti de Queiroz; Magna Suzana Alexandre Moreira; Luiz Henrique Rosa; Alysson Wagner Fernandes Duarte (Extremophiles, 2026)

Effect of dietary oil source on mitigating oxidative stress in tambaqui (Colossoma macropomum) juveniles subjected to acute cold stress - Renan Rosa Paulino; Raquel Tatiane Pereira; Alexandre Diógenes; Kátia Rodrigues Batista de Oliveira; Diana Carla Fernandes Oliveira; Helena Peres; Aires Oliva-Teles; Priscila Vieira Rosa (Aquaculture International, 2026)
This study assessed the effect of dietary oil sources on tambaqui ( Colossoma macropomum ) exposed to acute cold stress. Three different oil sources were incorporated individually at 7% into the diets: fish oil (FO), a blend of linseed and palm oils (LO), or corn oil (CO). These diets differed in their n-6/n-3 polyunsaturated fatty acid (PUFA) ratios, with n-3 PUFA derived from EPA + DHA (FO) or linolenic acid (LO) and n-6 PUFA from linoleic acid (CO). Fish (initial weight, 43 g) were fed ad libitum at 28°C for 49 days before the water temperature was reduced to 21°C within 40 min. Sampling occurred before (0h) and at 3h and 24h after cold stress. The dietary oil source had no significant effect on growth performance. Plasma cortisol and glucose levels were lowest at 3h post-stress, with FO-fed fish showing consistently reduced cortisol levels regardless of time. Plasma glucose was unaffected by diet composition. At 0h, fish fed the LO diet showed the lowest hepatic lipid peroxidation (LPO) levels, while at 3h and 24h, fish fed the FO and CO diets and the FO and LO diets showed lower LPO levels, respectively. Enzymatic activities of SOD, GPX, and GR exhibited a decline at 3 h and 24 h relative to the initial time point (0 h) across all dietary treatments. LPO levels also decreased post-stress, except in CO-fed fish at 24h. In conclusion, dietary n-3 PUFA improves oxidative stress resilience in tambaqui during acute cold exposure.

Acute toxicity and redox-modulating potential of nanoparticles loaded with phenolic compounds from cantaloupe melon (Cucumis melo L.) in zebrafish (Danio rerio) - Aslan Costa Trajano; Ana Carolina Luchiari; Yasmim Pessoa de Oliveira; Jéssica Anarellis Barbosa dos Santos; Beatriz Silva Lopes; Cristiane Fernandes de Assis; Hugo Alexandre Oliveira Rocha; Weslley de Souza Paiva; Susana Margarida Gomes Moreira; Pablo Felipe Ferreira Farias; Ana Heloneida de Araújo Morais; Thaís Souza Passos (Food Research International, 2026)

Multiple ecotoxicological effects of sublethal exposures to atmospheric particulate matter in two neotropical benthic species - Diego Ferreira Gomes; Thandy Junio da Silva Pinto; David Silva Alexandre; Michelly Pereira Soares; Raquel Aparecida Moreira; Hevelyn Plácido Gomes; Maira Rodrigues Lima; Evaldo Luiz Gaeta Espíndola; Odete Rocha; Marisa Narciso Fernandes (Journal of Hazardous Materials, 2026)

Law 22017/2023: a dire threat to the Cerrado's survival and Brazil's environmental leadership - Luciane Martins de Araújo; Manuel Eduardo Ferreira; José Antônio Tietzmann e Silva; Giovanni Martins de A. Mascarenhas; Altair Sales Barbosa; Mariana Pires de Campos Telles; José Alexandre Felizola Diniz-Filho; Ludgero Cardoso Galli Vieira; Geraldo Wilson Fernandes; Stephannie Fernandes; José Aluízio Ferreira Lima; Flávia de Figueiredo Machado (Environmental Development, 2026)

Evaluation of growth and chemical composition of forage consortia of grasses with tree species - Yamid Andres Perilla Melo; Alexandre Fernandes Perazzo; Shirlenne Ferreira Silva; Maysa Callado Moura; João Paulo Matos Pessoa; Walyson Alves de Araújo; Joana Floribella Lima da Silva; Ricardo Loiola Edvan (Agroforestry Systems, 2026)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

Greenhouse gases emissions and energy efficiency in ewe lambs fed hay from native Pantanal grasses - Jaine de Sousa Santos; Sandra Aparecida Santos; Roberto Cláudio Fernandes Franco Pompeu; Olivardo Facó; Alexandre Lima Ferreira; Delano de Sousa Oliveira; Arnaud Azevedo Alves; Alexandre Ribeiro Araújo; Marcos Cláudio Pinheiro Rogério (Tropical Animal Health and Production, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Epstein-barr virus (EBV) in cervical carcinoma detected by in situ hybridization targeting ebers and the viral genome - Álife Diêgo Lima Silva; Julia Graziele Alves Marelli; Maria Willaiara Lira Lopes; Myrella Tavares Rodrigues; Cecília Paz Lopes; José Nairton Coelho Silva; Sávio Samuel Feitosa Machado; Racquel Oliveira da Silva Souza; Maria Aparecida Tibúrcio; Alexandre Quental Sampaio; Isabelle Joyce de Lima Silva Fernandes; Claudia do Ó Pessoa; et al. (Brazilian Journal of Microbiology, 2025)

Paleoenvironmental reconstitution of a coastal tropical peatland and its relationship with the Holocene sea level variation (SE Brazil) - André Luiz Miranda Reis; Cynthia Fernandes Pinto da Luz; Ingrid Horák-Terra; Alexandre Christófaro Silva; Plínio Barbosa de Camargo; Pablo Vidal-Torrado (CATENA, 2025)

Differential effects of hypothermia and memantine in neonatal hypoxia-ischemia - Francielle Fernandes Spies; Ricardo Ribeiro Nunes; Isadora D’Avila Tassinari; Andrey Vinicios Soares Carvalho; Diorlon Nunes Machado; Rafael Bandeira Fabres; Carlos Alexandre Netto; Luciano Stürmer de Fraga (Metabolic Brain Disease, 2025)

Protection and safety of aluminum hydroxide adjuvant and chimeric antigen containing predicted epitopes from bacteria murC gene in Aeromonas hydrophila fish infection - Jojo Silva Rodrigues; Maria Roméria da Silva; Camila Aparecida Martins; Laura Alves Zuanon; Karina Ventura Boechat Martins; Pedro Segantini Tótola; Jheneze Guimarães Pereira Rocha; Mariana Grôppo Parma; Isabel Samila Lima Castro; Tarciza Fernandes Nascimento; Allan Rodrigues Pires; Filipe Silveira Azevedo; et al. (Fish & Shellfish Immunology, 2025)

Litter removal has long-lasting harmful effects on nutrient dynamics in a tropical secondary forest - Julia Isabella de Matos Rodrigues; Walmer Bruno Rocha Martins; Victor Pereira de Oliveira; Luiz Fernandes Silva Dionísio; Hiago Felipe Cardoso Pacheco; Marcos Alexandre Vieira Nascimento Filho; Manoel Tavares de Paula; Francisco de Assis Oliveira; Gustavo Schwartz (Plant and Soil, 2025)

Evaluation of the use of the myocardial performance index as a parameter of cardiac function in two experimental models of heart disease: myocardial infarction and pulmonary hypertension - Alexandre Luz de Castro; Patrick Turck; Angela Maria Vicente Tavares; Custódio José Gaspar; Alan Bahr; Alexsandra Zimmer; Tânia Regina G. Fernandes; Rafael Oliveira Fernandes; Vanessa Duarte Ortiz; Sílvio Tasca; Elissa Fernandes; Daniela Drosdowski; et al. (Pflügers Archiv - European Journal of Physiology, 2025)

The critically endangered Araripe Manakin (Antilophia bokermanni) is uninfected by, but probably susceptible to, haemosporidians in northeastern Brazil - Verônica L. Silva; João H. Oliveira; Pedro Henrique O. Pereira; Geovana S. Sandes; Érika M. Braga; Alexandre M. Fernandes (Journal of Ornithology, 2025)

Linking surface pCO2 variability to physical processes along a continental shelf–ocean transect in the southwestern Atlantic Ocean during austral autumn and winter - Cíntia Albuquerque; Gizyelle Miguel; Jannine M. Lencina-Avila; Luana Pinho; Humberto Marotta; Alexandre Macedo Fernandes; Elisa Nóbrega Passos; Leonardo Amora-Nogueira; Edmo Campos; Leticia Cotrim da Cunha (Frontiers in Marine Science, 2025)
The southwestern South Atlantic Ocean is an important global sink of atmospheric carbon dioxide (CO 2 ), driven by increased primary productivity in a nearby region where oligotrophic warm currents converge with nutrient-rich cold waters. However, uncertainties remain regarding CO 2 dynamics and the role of physical processes in CO 2 uptake across this region. Here, we assess variations in surface partial pressure of CO 2 ( p CO 2 ) and air–sea CO 2 fluxes in the Southwest Atlantic, along a transect from the continental shelf to the open ocean at 34.5°S during austral autumn 2018 and winter 2019. High-resolution spatial measurements of the temperature, salinity, and molar fraction of surface CO 2 were conducted. In autumn 2018, the shelf region acted as a source of CO 2 to the atmosphere (median of 3.2 mmol CO 2 m -2 d -1 ), which was partially offset by a sink (median of –2.5 mmol CO 2 m -2 d -1 ) in the open ocean. In contrast, the entire transect in winter 2019 presented median CO 2 emissions of ~1.5 mmol CO 2 m -2 d -1 , which differs from climatological estimates. The spatial and seasonal variations in surface ocean p CO 2 were linked to variable hydrodynamic processes, including water masses and mesoscale structures. Our findings reveal that, in one of the most productive oceanic waters worldwide, p CO 2 may be influenced by distinct continental inputs (e.g., rivers, runoff, and groundwater discharge) and water masses (e.g., Tropical Water, Plata Plume Water and Subtropical Shelf Water). Therefore, the local hydrodynamic processes can modulate high spatial and seasonal variability in CO 2 exchange at the ocean–atmosphere interface, with potential implications for regional and global carbon budgets. General results, such as climatological, cannot fully capture the influence of regional upwelling and continental water input, which highlights the importance of high-resolution regional observations.

Comparative analysis of sperm selection methods and their impact on in vitro fertility in the red-rumped agouti (Dasyprocta leporina) - Lhara Ricarliany Medeiros de Oliveira; Leonardo Vitorino Costa de Aquino; Antonia Beatriz Mendonça Pereira; Ana Lívia Rocha Rodrigues; Luanna Lorenna Vieira Rodrigues; Luana Grasiele Pereira Bezerra; Moacir Franco de Oliveira; Alexandre Rodrigues Silva; Alexsandra Fernandes Pereira (Research in Veterinary Science, 2025)

210Pb chronology assessing the historical microplastics dynamics and aging effects in urban areas with separate sewer systems and multiple-use reservoir - Fabiano T. Conceição; Alexandre M. Fernandes; Sarah G. Lacerda; Rodrigo B. Moruzzi; Naiara O. Santos; Rosa Busquets; Luiza C. Campos (Journal of Hazardous Materials, 2025)

Microbial and pest contamination in nuts: Radio frequency disinfestation and controlled atmosphere preservation – A review - Ângela Liberal; Ângela Fernandes; Jorge Moreira; Natércia Fernandes; Alexandre Gonçalves; Isabel C.F.R. Ferreira; Lillian Barros (Food Control, 2025)

Metabolic brain changes in post-acute COVID-19: systematic review and meta-analysis of [18F]-FDG-PET findings - Izabella Fernanda Bastos Siqueira; Lais Almeida Figueiredo; Camila Emanuele Moreira Fernandes; Leandro Pinheiro Cintra; Glauber Fernandes de Oliveira; Maria Angélica Rios; Ricardo Maciel; Rodrigo Ferretjans; Nathalia Sernizon Guimarães; Luiz Alexandre Viana Magno (Brain Structure and Function, 2025)

Influence of algal drift and morphodynamic conditions on the fish assemblages and feeding guilds in ocean-exposed tropical beaches - Alexandre da Gama Fernandes Vieira-Júnior; Breno Silva Macário; Steven J. Presley; Michael R. Willig; André Luiz Machado Pessanha (Estuarine, Coastal and Shelf Science, 2025)

Dietary supplementation with açai (Euterpe oleracea) improved the haemato-immunological parameters and growth performance of koi carp (Cyprinus Carpio Linnaeus, 1758) - Alexandre Vaz da Silva; Emilly Monteiro Lopes; Domickson Silva Costa; Gracienhe Gomes dos Santos; Caio Francisco Santana Farias; Paola Capistrano dos Santos; Ana Paula de Souza; Gabriele Bueno dos Anjos; Manoela Clemente Fernandes; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Marco Shizuo Owatari; et al. (Veterinary Research Communications, 2025)

Barbatimão bark as an alternative to sodium lasalocid in finishing diets for lambs: Carcass characteristics and meat quality - Aylpy R.D. Santos; Cristiane R. Barbosa; Carla G. Souza; Tatiane Fernandes; Renata A. Chagas; Samuel R. Navarro; Alexandre R.M. Fernandes; Fernando M. Vargas Junior (Meat Science, 2025)

Entropy-Based Measure of Rock Sample Heterogeneity Derived from Micro-CT Images - Luan Coelho Vieira da Silva; Júlio de Castro Vargas Fernandes; Felipe Bevilaqua Foldes Guimarães; Pedro Henrique Braga Lisboa; Carlos Eduardo Menezes dos Anjos; Thais Fernandes de Matos; Marcelo Ramalho Albuquerque; Rodrigo Surmas; Alexandre Gonçalves Evsukoff (Transport in Porous Media, 2025)

Microplastic contamination and biological alterations in Atlantic wild fish populations, and human health risks associated to fillet consumption - Sara C. Lourenço; Alexandre A.M.R.A. Aleluia; L. Gabriel A. Barboza; Xosé L. Otero; Sara C. Cunha; José O. Fernandes; Lúcia Guilhermino (Marine Environmental Research, 2025)

Substitution of silage by soybean hulls in tropical forage-based dairy cow production system during the dry season - Jéssica Coutinho Mezzomo da Silva; Carlos Eduardo Avelino Cabral; Isis Scatolin de Oliveira; Alexandre Lima de Souza; Camila Fernandes Domingues Duarte; Rodrigo Schaurich Mativi Righi; Eduarda Caroline Kichel Cuff; Lucas Gimenes Mota; Carla Heloisa Avelino Cabral (Tropical Animal Health and Production, 2025)

Spatial distribution and aggregation patterns of Triozoida limbata immatures in guava cultivars: implications for targeted pest management strategies - Isaias de Oliveira; Manoel A. Uchoa; Marcos Gino Fernandes; Odival Faccenda; Thiago Alexandre Mota; Inessa Steffany Torres de Oliveira (International Journal of Tropical Insect Science, 2025)

Organic carbon stocks across various land use systems in Sandy Ultisols and Oxisols in Brazil - Maria Cecília Vieira Totti; Yuri Lopes Zinn; Sérgio Henrique Godinho Silva; Bruno Montoani Silva; Fernanda Almeida Bócoli; Vanêssa Lopes de Faria; Andrés Olaya Montes; Salvador Francisco Acuña-Guzman; Alexandre Uezu; Laury Cullen Junior; Vinícius Ferreira Fernandes; Junior Cesar Avanzi (Geoderma Regional, 2025)

Total mixed ration silage based on cactus pear and cottonseed cake in the feeding of feedlot finished lambs - Danillo Marte Pereira; Juliana Silva de Oliveira; João Paulo de Farias Ramos; Iara Tamires Rodrigues Cavalcante; Francisco Naysson de Sousa Santos; Evandro de Sousa da Silva; Alexandre Fernandes Perazzo; Alberto Jefferson da Silva Macêdo; Paulo da Cunha Tôrres Júnior; Edson Mauro Santos (Tropical Animal Health and Production, 2025)

Unlocking the potential of Airborne LiDAR for direct assessment of fuel bulk density and load distributions for wildfire hazard mapping - Olivier Martin-Ducup; Jean-Luc Dupuy; Maxime Soma; Juan Guerra-Hernandez; Eva Marino; Paulo M. Fernandes; Ariadna Just; Jordi Corbera; Marion Toutchkov; Charlie Sorribas; Jerome Bock; Alexandre Piboule; et al. (Agricultural and Forest Meteorology, 2025)

Biochars from waste as an additive material in anaerobic co-digestion: Characterization and application in batch and semi-continuous systems - Isabela Mangerino Bortoloti Sicchieri; Thainara Camila Fernandes de Quadros; Mauricio Aparecido Bortoloti; Alexandre Teixeira de Souza; Helton Pereira Nogueira; Koiti Araki; Fernando Fernandes; Emília Kiyomi Kuroda (Fuel, 2025)

Phaseolus lunatus landraces from northeast Brazil: genetic diversity and anthracnose resistance - Vanessa Fernandes Soares; Glauber Santos Pereira; Alexandre de Oliveira Marques; Gildemberg Amorim Leal Junior (Genetic Resources and Crop Evolution, 2025)

Selenium agronomic biofortification and genotypic variability in physiological responses of cowpea plants under field conditions - Elcio Ferreira Santos; Eduardo Comparsi Filho; Luiz Eduardo Morais Fernandes Fontes; Mateus Andrey Pires Silva; Gutierres Nelson Silva; Alexandre Alonso Oliveira; Maurisrael de Moura Rocha; Vinícius Martins Silva; André Rodrigues Reis (Acta Physiologiae Plantarum, 2025)

Impression management in sustainability disclosures and information asymmetry: The case of Brazilian public companies - Alexandre Fernandes Monteiro; Rodrigo de Souza Gonçalves (Journal of Cleaner Production, 2025)

Molecular detection and phylogenetic analysis of Leptospira interrogans and Leptospira borgpetersenii in cats from Central region of Rio Grande do Sul state, Brazil - Bruna Carolina Ulsenheimer; Alexandre Alberto Tonin; Ana Eucares von Laer; Helton Fernandes dos Santos; Luís Antônio Sangioni; Rafael Fighera; Matheus Yuri dos Santos; Daniela Isabel Brayer Pereira; Luciana Pötter; Sônia de Avila Botton (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

The Interaction Between the Linnean and Darwinian Shortfalls Affects Our Understanding of the Evolutionary Dynamics Driving Diversity Patterns of New World Coralsnakes - Lívia Estéfane Fernandes Frateles; Guilherme Rogie Gonçalves Tavares; Gabriel Nakamura; Nelson Jorge da Silva; Levi Carina Terribile; José Alexandre F. Diniz‐Filho (Journal of Biogeography, 2025)
Aim In this study, we sought to understand how the Linnean shortfall (i.e., the lack of knowledge about species taxonomy) interacts with the Darwinian shortfall (i.e., the lack of knowledge about phylogenetic relationships among species), which potentially jeopardises geographical patterns in estimates of speciation rates. Location New World. Taxon Coralsnakes (Serpentes: Elapidae). Methods We created an index of taxonomic uncertainty (ITU) that measures the likelihood of current species being split after undergoing future taxonomic revisions. The ITU was used in simulations where species with higher taxonomic uncertainty had a higher likelihood of having their phylogenetic branches split, generating new hypothetical species along their geographic ranges. We estimated the speciation rates before and after the split of taxonomically uncertain species. Results We found that a high number of coralsnake species display substantial taxonomic uncertainty, positively correlated with the latitude of the species' geographical range centroid. The estimated speciation rates based on currently available data have a weak relationship with latitude. However, after incorporating taxonomic uncertainty into the phylogeny, we detect a higher positive correlation between speciation rate and latitude. Main Conclusions The observed change in speciation rates following the incorporation of taxonomic uncertainty highlights how such uncertainty can undermine the empirical evaluation of geographical patterns in speciation rates, revealing an interaction between the latitudinal taxonomic gradient and the latitudinal diversity gradient. Given that taxonomic changes can alter the number of species recognised as valid over time, our study highlights the need to incorporate taxonomic uncertainty into macroecological and macroevolutionary studies, enhancing the robustness of patterns inferred from these data.

Cyto and genotoxicity induced by acute exposure to Novacron® Bold Deep Navy dye on Astyanax lacustris can be reduced after treatment through a vertical flow constructed wetland system - Josiane Rodrigues Rocha da Silva; Camila Oliveira de Andrade; Anna Carla Ribeiro; Paula Derksen Macruz; Rosângela Bergamasco; Carlos Alexandre Fernandes (Environmental Science and Pollution Research, 2024)

Determination of mometasone furoate solubility, using deep eutectic systems, and topical formulation- experimental and computational studies - Rita Craveiro; Ângelo Rocha; Cláudio Fernandes; Ana Rita C. Duarte; Joana Marto; Alexandre Paiva (Sustainable Chemistry and Pharmacy, 2024)

Novel beer bitterness measurement instrument using optical fiber sensor - Renato Luiz Faraco Filho; Felipe Oliveira Barino; João Victor Calderano; Deivid Campos; Ítalo Fernandes Valle Alvarenga; André William Paviani Manhas; Alexandre Bessa dos Santos (Journal of Food Engineering, 2024)

Antibacterial activity of functionalized natural zeolites (NZ-AgNPs) and its application in bacteriological water treatment and commercial paints - Anna Carla Ribeiro; Alessandra Marjorie de Oliveira; Laiza Bergamasco Beltran; Alexandre Diório; Grace Anne Vieira Magalhães-Ghiotto; Benício Alves de Abreu Filho; Elizabeth da Costa Neves Fernandes de Almeida Duarte; Rosângela Bergamasco (Environmental Nanotechnology, Monitoring & Management, 2024)

Supplementation with 25-hydroxicolecalciferol increases the nutritional efficiency and carcass growth of grazing Nellore young bulls - Fernanda S. Mudado; Melissa B. Silveira; Henrique J. Fernandes; Alexandre Perdigão; Diego M.M. dos Santos; Thomas H.R. da Silva; Jarbas M. da Silva Júnior; Isabelle E. de Matos; Victor V. de Carvalho; Tiago S. Acedo; Aline G. da Silva (Animal Feed Science and Technology, 2024)

In Vivo Test to Evaluate the Cytotoxicity and Genotoxicity of Natural Zeolite (NZ) Functionalized with Silver Nanoparticles (NZ-AgNPs) on Erythrocytes of Yellowtail Tetra Fish Astyanax lacustris - Josiane Rodrigues Rocha da Silva; Camila Oliveira de Andrade; Anna Carla Ribeiro; Paula Derksen Macruz; Elizabeth da Costa Neves FernandesAlmeida Dua; Rosângela Bergamasco; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes (Biological Trace Element Research, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

ER stress improvement by aerobic training or enalapril differently ameliorates pathological cardiac remodeling in obese mice - Amanda Conceição Pimenta Salles; Beatriz Alexandre-Santos; Thais de Souza Carvalho; Ana Beatriz Proença; Vinicius Sepúlveda-Fragoso; Tiago Fernandes; Edilamar Menezes Oliveira; Antonio Claudio Lucas da Nóbrega; Eliete Dalla Corte Frantz; D’Angelo Carlo Magliano (Molecular and Cellular Biochemistry, 2024)

Pseudoplagiostoma humilis sp. nov., a New Fungal Species Causing Shoot Blight and Dieback in Anacardium humile in Brazil - Luiz Pedro Pereira Magalhães; Nilza de Lima Pereira Sales; Patrícia Doerl Barroso; Rildo Alexandre Fernandes da Silva; Danilo Batista Pinho; José Cola Zanuncio; André Costa da Silva (Current Microbiology, 2024)

Ultrastructural evaluation of the oocytes and spermatozoa of the scleractinian coral Mussismilia harttii - Wanderson Valente; Cláudia Kelly Fernandes da Cruz; Jener Alexandre Sampaio Zuanon; Gleide Fernandes de Avelar; Leandro Godoy (Tissue and Cell, 2024)

Ultrasound-assisted extraction of anthocyanins from grape pomace using acidified water: Assessing total monomeric anthocyanin and specific anthocyanin contents - Betina Louise Angioletti Decker; Elenilson de Godoy Alves Filho; Lorena Mara Alexandre e Silva; Paulo Riceli Vasconcelos Ribeiro; Edy Sousa de Brito; Fabiano André Narciso Fernandes; Thatyane Vidal Fonteles; Sueli Rodrigues (Food Research International, 2024)

Flooding and fire frequency promotes beta diversity in tree and non-tree species in tropical wetlands - Bruno Henrique dos Santos Ferreira; Maxwell da Rosa Oliveira; Bruno Arguelho Arrua; Vivian Ayumi Fujizawa Nacagava; Rafaela Aparecida Mariano Fernandes; Alexandre de Matos Martins Pereira; Andréia de Carvalho Santos; Ademilson Costa; Mesaque Rocha; Silvio Xavier; Rubens Aquino Ferraz; Arnildo Pott; et al. (Forest Ecology and Management, 2024)

Speciation in savanna birds in South America: The case of the Least Nighthawk Chordeiles pusillus (Aves: Caprimulgidae) in and out of the Amazon - Alexandre M. Fernandes; Mario Cohn-Haft; Luís Fábio Silveira; Alexandre Aleixo; Nathália Nascimento; Urban Olsson (Molecular Phylogenetics and Evolution, 2024)

Integrating policy, data and technology in pursuing effective management of ecosystem services - Maíse Soares de Moura; Victor Cordeiro da Silva; Alexandre Ferreira Menezes; Fernando Antonio Leal Pacheco; Luís Filipe Sanches Fernandes; Teresa Cristina Tarlé Pissarra; Adriana Monteiro da Costa (Journal of Environmental Management, 2024)

Reversal of high-fat diet-induced cognitive impairment and oxidative stress in the brain through Zingiber officinale supplementation - Thais Fernandes Luciano; Claudio Teodoro de Souza; Jade de Oliveira; Alexandre Pastoris Muller (Metabolic Brain Disease, 2024)

Dynamics of dissolved inorganic carbon (DIC) and stable C isotope ratios (δ13CDIC) in a tropical watershed with diversified land use in São Paulo State, Brazil - Fabiano Tomazini da Conceição; Alexandre Martins Fernandes; Rodrigo Braga Moruzzi; Jefferson Mortatti (Science of The Total Environment, 2024)

The effect of acute exposure of yellowtail tetra fish Astyanax lacustris (Lütken, 1875) to the glyphosate-based herbicide Templo® - Camila Oliveira de Andrade; Josiane Rodrigues Rocha da Silva; Pablo Americo Barbieri; Luciana Andrea Borin-Carvalho; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Harnessing crop models and machine learning for a spatial-temporal characterization of irrigated rice breeding environments in Brazil - Alexandre Bryan Heinemann; Germano Costa-Neto; David Henriques da Matta; Igor Kuivjogi Fernandes; Luís Fernando Stone (Field Crops Research, 2024)

Reconstruction of the marine carbonate system at the Western Tropical Atlantic: trends and variabilities from 20 years of the PIRATA program - Carlos Augusto Musetti de Assis; Luana Queiroz Pinho; Alexandre Macedo Fernandes; Moacyr Araujo; Leticia Cotrim da Cunha (Frontiers in Marine Science, 2024)
The Western Tropical Atlantic Ocean (WTAO) is crucial for understanding CO 2 dynamics due to inputs from major rivers (Amazon and Orinoco), substantial rainfall from the Intertropical Convergence Zone (ITCZ), and CO 2 -rich waters from equatorial upwelling. This study, spanning 1998 to 2018, utilized sea surface temperature (SST) and sea surface salinity (SSS) data from the PIRATA buoy at 8°N 38°W to reconstruct the surface marine carbonate system. Empirical models derived total alkalinity (TA) and dissolved inorganic carbon (DIC) from SSS, with subsequent estimation of pH and f CO 2 from TA, DIC, SSS, and SST data. Linear trend analysis showed statistically significant temporal trends: DIC and f CO 2 increased at a rate of 0.7 µmol kg-1 year-1 and 1.539 µatm year-1, respectively, and pH decreased at a rate of -0.001 pH units year-1, although DIC did not show any trend after data was de-seasoned. Rainfall analysis revealed distinct dry (July to December) and wet (January to June) seasons, aligning with lower and higher freshwater influence on the ocean surface, respectively. TA, DIC, and pH correlated positively with SSS, exhibiting higher values during the dry season and lower values during the wet season. Conversely, f CO 2 correlated positively with SST, showcasing higher values during the wet season and lower values during the dry season. This emphasizes the influential roles of SSS and SST variability in CO 2 solubility within the region. Finally, we have analysed the difference between TA and DIC (TA-DIC) as an indicator for ocean acidification and found a decreasing trend of -0.93 ± 0.02 μmol kg-1 year-1, reinforcing the reduction in the surface ocean buffering capacity in this area. All trends found for the region agree with data from other stations in the tropical and subtropical Atlantic Ocean. In conclusion, the use of empirical models proposed in this study has proven to help filling the gaps in marine carbonate system data in the Western Tropical Atlantic.

Phenolic-rich extract from Bryophyllum pinnatum leaf cultivated under drought stress conditions modulates the antioxidant and anti-inflammatory response - Natasha Lorenna Ferreira da Silva; Renato Dantas-Medeiros; Emanuella de Aragão Tavares; Dayanne Lopes Porto; Valéria Costa da Silva; Jacinthia Beatriz Xavier-Santos; Júlia Gabriela Ramos Passos; Weslley de Souza Paiva; Hugo Alexandre de Oliveira Rocha; Matheus de Freitas Fernandes-Pedrosa; Júlia Morais Fernandes; Silvana Maria Zucolotto (Phytochemistry Letters, 2024)

Texture prediction of natural soils in the Brazilian Amazon through proximal sensors - Quésia Sá Pavão; Paula Godinho Ribeiro; Gutierre Pereira Maciel; Sérgio Henrique Godinho Silva; Suzana Romeiro Araújo; Antonio Rodrigues Fernandes; José Alexandre Melo Demattê; Pedro Walfir Martins e Souza Filho; Silvio Junio Ramos (Geoderma Regional, 2024)

Systematic screening of synthetic organochalcogen compounds with anticancer activity using human lung adenocarcinoma spheroids - Jéssica Eduarda dos Santos Batista; Mariele Borkowski Rodrigues; Ivi Juliana Bristot; Valquíria Silva; Silvia Bernardy; Oscar Endrigo Dorneles Rodrigues; Luciano Dornelles; Fabiano Barbosa Carvalho; Francisca Joseli Freitas de Sousa; Marilda da Cruz Fernandes; Geancarlo Zanatta; Félix Alexandre Antunes Soares; et al. (Chemico-Biological Interactions, 2024)

Carbon and nitrogen, humic and labile fractions in soil under clonal eucalyptus stands from cerrado - Wendel dos Santos Moraes; Luiz Fernandes Silva Dionisio; Gustavo Schwartz; Juliana Andrade Pereira; Jossimara Ferreira Damascena; Felipe Alexandre Rizzo; Alberto Bentes Brasil Neto; Camila de Almeida Milhomem; José Maria Arcanjo Alves; Renisson Neponuceno Araujo Filho; Renato de Almeida Sarmento; Alinne da Silva; et al. (European Journal of Forest Research, 2024)

Leptospira borgptersenii and Leptospira interrogans identified in wild mammals in Rio Grande do Sul, Brazil - Bruna Carolina Ulsenheimer; Alexandre Alberto Tonin; Ana Eucares von Laer; Helton Fernandes dos Santos; Luís Antônio Sangioni; Rafael Fighera; Matheus Yuri dos Santos; Daniela Isabel Brayer; Sônia de Avila Botton (Brazilian Journal of Microbiology, 2024)

Linnean shortfall and space‐time patterns in species description of New World coralsnakes (Serpentes: Elapidae) - Lívia Estéfane Fernandes Frateles; Nelson Jorge da Silva; Levi Carina Terribile; José Alexandre Felizola Diniz‐Filho (Zoologica Scripta, 2024)
The magnitude of life on Earth and human limitations hinder the understanding of even the most basic aspects of biodiversity, such as the identity of species inhabiting the Earth, the so‐called Linnean shortfall. Evaluating patterns in species description dates and their relationship with macroecological variables can help guide where taxonomic efforts should be focused. Therefore, we aim to assess the Linnean shortfall in the knowledge of New World coralsnake biodiversity. We modelled species description dates and estimated that approximately one‐third of the coralsnake diversity remains unknown. The undescribed species are evolutionarily closely related to the already described species. Moreover, recently described species in the group have more restricted geographic ranges and tend to be small‐bodied. The western Amazon and the dry diagonal (i.e. Caatinga, Cerrado, and Chaco) are the areas with the oldest description dates. However, assemblages in these areas have the largest average geographic distances to the type locality of their species, suggesting that little taxonomic effort has been dedicated intrinsically to these regions. We suggest that allocating taxonomic efforts to the dry diagonal and the use of integrative taxonomic techniques for better species delimitation are imperative to fill the Linnean shortfall for the New World coralsnakes.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

In silico and in vitro elastase inhibition assessment assays of rosmarinic acid natural product from Rosmarinus officinalis Linn - Ester Gonçalves de Jesus; Fernanda Fernandes de Souza; João Victor Andrade; Márcio Luís Andrade e Silva; Wilson R. Cunha; Rafael Corrêa Ramos; Othon Souto Campos; Jorge Alexandre Nogueira Santos; Mario F. C. Santos (Natural Product Research, 2024)

Mathematical models for predicting protodioscin in tropical forage grasses - Juliana Caroline Santos Santana; Gelson dos Santos Difante; Jéssica Gomes Rodrigues; Marislayne de Gusmão Pereira; Henrique Jorge Fernandes; Camila Celeste Brandão Ferreira Ítavo; Vanessa Zirondi Longhini; Alexandre Menezes Dias; Luís Carlos Vinhas Ítavo (Toxicon, 2024)

Erythrocyte alterations in specimens of Danio rerio caused by exposure to metformin - Pablo Americo Barbieri; Luara Lupepsa; Brennda Ribeiro Paupitz; Camila Oliveira de Andrade; Adriana Aparecida Sinópolis Gigliolli; Ana Luiza de Brito Portela-Castro; Ricardo Pereira Ribeiro; Carlos Alexandre Fernandes; Luciana Andreia Borin-Carvalho (Environmental Toxicology and Pharmacology, 2024)

Nutritional strategies, performance, digestibility, and carcass traits of Santa Ines and Rabo Largo breeds in a tropical climate - Anderson Lopes Pereira; Michelle de Oliveira Maia Parente; Edegleicia Alves de Sousa; Arnaud Azevedo Alves; Anderson de Moura Zanine; Daniele de Jesus Ferreira; Alexandre Fernandes Perazzo; Francisca Cláudia da Silva de Sousa; Luana França dos Anjos; Hyanne Costa Lima; Miguel Arcanjo Moreira Filho; Hactus Souto Cavalcanti; et al. (Tropical Animal Health and Production, 2024)

Long-term preservation of established fibroblast lines from six‐banded armadillos (Euphractus sexcintus, Linnaeus, 1758) by extended passage and cryopreservation - Denilsa Pires Fernandes; Érika Almeida Praxedes; João Vitor da Silva Viana; Maria Valéria de Oliveira Santos; Alexandre Rodrigues Silva; Carlos Iberê Alves Freitas; Alexsandra Fernandes Pereira (In Vitro Cellular & Developmental Biology - Animal, 2024)

Concentrations, sources and risks of polycyclic aromatic hydrocarbons in sediments from the Parnaiba Delta basin, Northeast Brazil - Analine D.C. Andrade; Gabrielle M. Fernandes; Davi A. Martins; Rivelino M. Cavalcante; Michel R.B. Chaves; Alexandre A. de Souza; Jeremias P. da S. Filho; Ronaldo F. Nascimento; Sidney G. de Lima (Chemosphere, 2024)

Adaptability and stability of black bean genotypes with normal and early cycle - Moisés Ambrósio; Rogério Figueiredo Daher; Raiane Mariani Santos; Josefa Grasiela Silva Santana; Ana Kesia Faria Vidal; Maxwel Rodrigues Nascimento; Cleudiane Lopes Leite; Alexandre Gomes de Souza; Rafael Souza Freitas; Wanessa Francesconi Stida; João Esdras Calaça Farias; Benedito Fernandes de Souza Filho; et al. (Euphytica, 2024)

A new adsorptive 3D–printed sampling device for simultaneous determination of 63 urinary organic acids by LC–MS/MS - Mariana Zuccherato Bocato; Reverson Fernandes Quero; Anthony Alexandre Weil; Cibele Aparecida Cesila; Joseph Adewuyi Adeyemi; Fernando Barbosa Jr (Analytica Chimica Acta, 2024)

Açaí (Euterpe oleracea Mart.) green synthesis of silver nanoparticles: antimicrobial efficacy and ecotoxicological assessment - Andy Joel Taipe Huisa; Marcelo Estrella Josende; Marcos Alexandre Gelesky; Daniela Fernandes Ramos; Gerardo López; Fabiano Bernardi; José María Monserrat (Environmental Science and Pollution Research, 2024)

Exploring the neuroprotective potential of antimicrobial peptides from Dinoponera quadriceps venom against pentylenetetrazole-induced seizures in vivo - Livia Correia Fernandes Paes; Dânya Bandeira Lima; Daniel Moreira Alves da Silva; José Tiago Valentin; Pedro Everson Alexandre de Aquino; Alicia Belén García-Jareño; Mar Orzaéz; Marta Maria de França Fonteles; Alice Maria Costa Martins (Toxicon, 2024)

The end of an entire biome? World's largest wetland, the Pantanal, is menaced by the Hidrovia project which is uncertain to sustainably support large-scale navigation - Karl M. Wantzen; Mario Luis Assine; Ieda Maria Bortolotto; Debora Fernandes Calheiros; Zilca Campos; Agostinho Carlos Catella; Rafael Morais Chiaravalotti; Walter Collischonn; Eduardo Guimarães Couto; Catia Nunes da Cunha; Geraldo Alves Damasceno-Junior; Carolina Joana da Silva; et al. (Science of The Total Environment, 2024)

Effects of diets differing in the concentrate-to-roughage ratio on meat quality and fatty acids composition in abomasal digesta and meat from thin-tail and fat-tail Brazilian ovine breeds - Luana França dos Anjos; Rui José Branquinho de Bessa; Henrique Nunes Parente; Susana Paula Alves; Aline Vieira Landim; Anderson de Moura Zanine; Anderson Lopes Pereira; Graziele Silva de Oliveira; Daniele de Jesus Ferreira; Alexandre Fernandes Perazzo; Mayara Raposo dos Santos; Michelle de Oliveira Maia Parente (Small Ruminant Research, 2023)

Do tides equally influence the reproductive cycle of two symbiotic estuarine shrimp? - Rodrigo Guéron; Douglas Fernandes Rodrigues Alves; Alexandre Oliveira Almeida (Regional Studies in Marine Science, 2023)

Geographic Drivers of Genetic and Plumage Color Diversity in the Blue-Crowned Manakin - Pedro Paulo; Fernando Henrique Teófilo; Carolina Bertuol; Érico Polo; Andre E. Moncrieff; Lucas N. Bandeira; Claudia Nuñez-Penichet; Igor Yuri Fernandes; Mariane Bosholn; Arielli F. Machado; Leilton Willians Luna; Willian Thomaz Peçanha; et al. (Evolutionary Biology, 2023)

Identification of pegmatites zones in Muiane and Naipa (Mozambique) from Sentinel-2 images, using band combinations, band ratios, PCA and supervised classification - Ubaldo Gemusse; Joana Cardoso-Fernandes; Alexandre Lima; Ana Teodoro (Remote Sensing Applications: Society and Environment, 2023)

Nutritional and chemical composition of Alpinia zerumbet leaves, a traditional functional food - Jefferson Diocesano da Cruz; Maria A. Mpalantinos; Laena Rebouças de Oliveira; Tainara Garcia Branches; Alexandre Xavier; Francisca das Chagas do A. Souza; Jaime P. Lopes Aguiar; José Luiz P. Ferreira; Jefferson Rocha de Andrade Silva; Ana Claudia Fernandes Amaral (Food Research International, 2023)

Spray-chilling system in the initial cooling process of swine half carcasses - Alessandra Pereira dos Santos; Fabiana Ribeiro Caldara; Alexandre Rodrigo Mendes Fernandes; Maria Fernanda de Castro Burbarelli; Bruna de Souza Eberhart; Jean Kaique Valentim; Ibiara Correia de Lima Almeida Paz; Rodrigo Garófallo Garcia; Agnês Markiy Odakura (Meat Science, 2023)

Pectin hydrogels modified with montmorillonite: Case studies for the removal of dyes and herbicides from water - Wilson Bokorny Fernandes Filho; Sedami Tozoun Romain Agassin; Karine Priscila Naidek; Alexandre Tadeu Paulino (Journal of Environmental Chemical Engineering, 2023)

Digital Rock Analysis Based on X-ray Computed Tomography of a Complex Pre-salt Carbonate Reservoir from the Santos Basin, SE Brazil - Gabriela Fernandes Matheus; Mateus Basso; João Paulo da Ponte Souza; Alexandre Campane Vidal (Transport in Porous Media, 2023)

Isotopic niches of juvenile and adult green turtles (Chelonia mydas) in feeding and nesting areas in Brazil, southwestern Atlantic Ocean - Amanda Fernandes; Leandro Bugoni; Adalto Bianchini; Cleverson Zapelini; Alexandre Schiavetti (Frontiers in Marine Science, 2023)
Stable isotope analysis is an approach that allows inferring feeding ecology and trophic structure of populations, especially for species that are difficult to observe in natural habitats, such as marine turtles. This study investigated the niche breadth of adult and juvenile green sea turtles ( Chelonia mydas ) through δ 15 N and δ 13 C values in carapace scutes. During 2017 and 2018, tissues were collected from juveniles in a feeding area in southeastern Brazil ( n = 60) and from adults in a nesting area in northeastern Brazil, at Fernando de Noronha ( n = 21). Our results revealed no temporal variations in the isotopic values of adult green turtles and the mean δ 15 N values are compatible with the isotopic values of primarily herbivorous animals. In southeastern Brazil, the δ 13 C values and isotopic niche breadth differences observed in juvenile green turtles suggest that variations in habitat (i.e., channel between the municipalities of Ilhabela and São Sebastião - “SSC” and region comprising the other two municipalities of Ubatuba and Caraguatatuba - “CAU”, as defined in this study based on oceanographic current dynamics) can influence their isotopic niche. The isotopic values observed in juvenile green turtles demonstrated a high degree of feeding behavior plasticity and individual variability, which were possibly influenced by the dynamic of oceanographic currents and seasonal nutrient inputs. These findings help to elucidate the feeding behavior of green turtles at different life stages and the potential influence of oceanographic current dynamics in key feeding sites for juvenile green turtles.

Li-rich pegmatites and related peraluminous granites of the Fregeneda-Almendra field (Spain-Portugal): A case study of magmatic signature for Li enrichment - Encarnación Roda-Robles; Romeu Vieira; Alexandre Lima; Jon Errandonea-Martin; Alfonso Pesquera; Joana Cardoso-Fernandes; Idoia Garate-Olave (Lithos, 2023)

Temperature stratification in the Guanabara Bay and its relationship with wind-induced coastal upwelling off Cabo Frio, Brazil - Alexandre Macedo Fernandes; Elisa Nóbrega Passos; Paulo Henrique Rezende Calil; Gleyci Aparecida Oliveira Moser; Eduardo Negri de Oliveira; Rogério Pinto Espíndola (Estuarine, Coastal and Shelf Science, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Deontic signs increase control monitoring: evidence from a modified traffic flanker task - Teresa Garcia-Marques; Pedro Figueira; Alexandre Fernandes; João Martins (Cognitive Processing, 2023)
Deontic norms are expected to impose individuals’ control over their behavior. In this paper, we address such norms presented in traffic signs and test their influence over executive control functions. For Experiment 1, we develop a traffic flanker task in which the typical neutral arrows are replaced with traffic prohibition/obligation signs. Experiment 2 isolated the deontic aspect of the signs using simple arrows on red, blue, and green backgrounds and either primed them to be interpreted as traffic signs or as elements of a gaming console controller. Results in both studies show evidence of controlling context interferences more efficiently when dealing with deontic (traffic) signs than with simple arrows (Experiment 1) or with similar perceptive targets when primed with a deontic context than with a gaming context (Experiment 2). In both studies, obligation/blue signs mitigate flanker effects less than prohibition/red signs. Stimuli color affects the alertness of the cognitive system, with the color red being, by itself, a cue for increased control. Based on temporal analysis, we further discuss these results as evidence of an increase in proactive control that aims to prevent the occurrence of undesirable influence.

Evaluation of Covalent Organic Frameworks for the low-cost, rapid detection of Shiga Toxin-producing Escherichia coli in ready-to-eat salads - Ana Costa-Ribeiro; Sarah Azinheiro; Soraia P.S. Fernandes; Alexandre Lamas; Marta Prado; Laura M. Salonen; Alejandro Garrido-Maestu (Analytica Chimica Acta, 2023)

Do wave exposure and drifting algae drive the functional diversity of fishes in tropical ocean-exposed sandy beaches? - Alexandre da Gama Fernandes Vieira Júnior; Éden Hávila Lima Guedes; Gitá Juan Soterorudá Brito; Juan Alves Pereira; Marina Dolbeth; e André Luiz Machado Pessanha (Estuarine, Coastal and Shelf Science, 2023)

Antimicrobial activity and chemical profile of wood vinegar from eucalyptus (Eucalyptus urophylla x Eucalyptus grandis - clone I144) and bamboo (Bambusa vulgaris) - Gil Sander Próspero Gama; Alexandre Santos Pimenta; Francisco Marlon Carneiro Feijó; Caio Sérgio Santos; Bruno Caio Chaves Fernandes; Moacir Franco de Oliveira; Elias Costa de Souza; Thays V. C. Monteiro; Maíra Fasciotti; Tatiane Kelly Barbosa de Azevedo; Rafael Rodolfo de Melo; Ananias Francisco Dias Júnior (World Journal of Microbiology and Biotechnology, 2023)

Conditioned medium of mesenchymal stem cells: application in mares with endometrial fibrosis - Fabiano Trevisan da Rocha; Janislene Mach Trentin; Henrique Boll de Araújo Bastos; Rômulo Oliveira Fernandes da Silva; Matheus Souto de Freitas; Rodrigo Costa Mattos; Nélson Alexandre Kreztmann Filho; Mara Iolanda Batistella Rubin (Journal of Equine Veterinary Science, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Modeling and optimization of the pyrolysis oil production process from polypropylene for the production of aviation kerosene - Heraclito Alexandre dos Santos; Igor José Boggione Santos; Cristiane Medina Finzi Quintão; Vagner Fernandes Knupp; Renata Carolina Zanetti Lofrano; Eliane Cristina de Oliveira; Gisella Lamas Samanamud; Mateus de Souza Amaral; Alexandre Boscaro França; Mariana Arruda Pereira; Matheus Teixeira Araújo Silva; Carla Cristina Almeida Loures; et al. (Clean Technologies and Environmental Policy, 2023)

Use of a product based on wood vinegar of Eucalyptus clone I144 used in the control of bovine mastitis - Bismark Alves da Silva; Francisco Marlon Carneiro Feijó; Nilza Dutra Alves; Alexandre Santos Pimenta; Leon Denner Moreira Benicio; Enilson Claudio da Silva Júnior; Caio Sérgio Santos; Alexsandra Fernandes Pereira; Yasmin Beatriz França Moura; Gil Sander Prospero Gama; Evilasio de Souza Lima Neto (Veterinary Microbiology, 2023)

Cadmium effects on the freshwater teleost Prochilodus lineatus: Accumulation and biochemical, genotoxic, and behavioural biomarkers - Alexandre Oliveira Fernandes da Silva; Vanessa Bezerra; Paulo Cesar Meletti; Juliana Delatim Simonato; Claudia Bueno dos Reis Martinez (Environmental Toxicology and Pharmacology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Potential in vitro action of an adenosine analog and synergism with penicillin against Corynebacterium pseudotuberculosis - Pedro Negri Bernardino; Carolina Lechinski de Paula; Ana Flávia Marques Pereira; Márcio Garcia Ribeiro; Vasco Ariston de Carvalho Azevedo; Alexandre Secorun Borges; Ary Fernandes-Júnior; José Paes Oliveira-Filho (Brazilian Journal of Microbiology, 2023)

A review of Cameroonian medicinal plants with potentials for the management of the COVID-19 pandemic - Evariste Fongnzossie Fedoung; Achille Bernard Biwole; Christine Fernande Nyangono Biyegue; Marlene Ngansop Tounkam; Patrick Akono Ntonga; Véronique Priscille Nguiamba; Damien Marie Essono; Preasious Forbi Funwi; Calvin Tonga; Guy Merlin Nguenang; Victor Kemeuze; Denis Jean Sonwa; et al. (Advances in Traditional Medicine, 2023)

Low dose of cyclosporine A disrupts sperm parameters and testosterone levels reversibly in mice - Gláucia Eloisa Munhoz de Lion Siervo; Noemia Aparecida Partelli Mariani; Alan Andrew S. Silva; Ana Paula Franco Punhagui-Umbelino; Ivana Regina da Costa; Alexandre Dorth de Andrade; Erick J.R. Silva; Glaura Scantamburlo Alves Fernandes (Toxicology and Applied Pharmacology, 2023)

Genotoxicity and cytotoxicity of textile production effluents, before and after Bacillus subitilis bioremediation, in Astyanax lacustris (Pisces, Characidae) - Josiane Rodrigues Rocha da Silva; Angelivia Gregorio; Ana Luiza de Brito Portela-Castro; Carlos Alexandre Fernandes (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Intake, digestibility, nitrogen balance and performance in lamb fed spineless cactus silage associated with forages adapted to the semiarid environment Spineless cactus silages in diets for lambs - Tiago Santos Silva; Gherman Garcia Leal de Araújo; Edson Mauro Santos; Juliana Silva de Oliveira; Paulo Fernando Andrade Godoi; Glayciane Costa Gois; Alexandre Fernandes Perazzo; Ossival Lolato Ribeiro; Silvia Helena Nogueira Turco; Fleming Sena Campos (Livestock Science, 2023)

FK506 impairs neutrophil migration that results in increased polymicrobial sepsis susceptibility - Vanessa de Fátima Borges; Leticia Selinger Galant; Alexandre Kanashiro; Fernanda Vargas e Silva Castanheira; Valter Vinícius Silva Monteiro; Diego Ângelo Duarte; Filipe Camargo Rodrigues; Camila Meirelles de Souza Silva; Ayda Henriques Schneider; Guilherme Cesar Martelossi Cebinelli; Mikhael Haruo Fernandes de Lima; João Paulo de Biaso Viola; et al. (Inflammation Research, 2023)

Mainstreaming Flora Conservation Strategies into the Mitigation Hierarchy to Strengthen Environmental Impact Assessment - Taís Nogueira Fernandes; Fernando Marino Gomes dos Santos; Flávio Dayrell Gontijo; João Alves da Silva Filho; Alexandre Franco Castilho; Luis Enrique Sánchez (Environmental Management, 2023)
The application of the mitigation hierarchy (MH) to mining projects is challenging in situations of locational overlap between endemic flora and mineral deposits. We review flora surveys conducted in connection with the environmental impact assessment of several iron ore mining projects in an area of high degree of endemism in Eastern Amazon to discuss the practical implications of anticipating conservation strategies. Desktop studies and secondary data review were conducted to guide field searches to determine the distribution of endemic flora, resulting in 45 out of 46 endemic plant species having their known distribution extended to new areas. A framework for positioning flora conservation strategies in the MH is presented. Specific habitat requirements and scarce knowledge about endangered and endemic flora species are a conservation obstacle, since essential information to define species conservation strategies may be lacking. We show that anticipating conservation strategies can minimize time-lag uncertainties related to restoration success and biodiversity offsets. The more effort is placed in the preventative steps of the MH, the smaller the time-lag between impact (biodiversity losses) and conservation outcomes (biodiversity gains), decreasing uncertainties and reducing risks to biodiversity.

Field evaluation of industrial non-food crops for phytomanaging a metal-contaminated dredged sediment - Alexandre Perlein; Valérie Bert; Marcella Fernandes de Souza; Arnaud Papin; Erik Meers (Environmental Science and Pollution Research, 2023)

The Late Jurassic–Early Cretaceous lacustrine facies and ichnofossils of the Parnaíba Basin, Brazil: A record of bioactivity in response to post-CAMP thermal subsidence in West Gondwana - Argel de Assis Nunes Sodré; Joelson Lima Soares; Afonso César Rodrigues Nogueira; Alexandre Ribeiro Cardoso; Renan Fernandes dos Santos (Sedimentary Geology, 2023)

Continuous removal of pharmaceutical drug chloroquine and Safranin-O dye from water using agar-graphene oxide hydrogel: Selective adsorption in batch and fixed-bed experiments - Caroline Maria Bezerra de Araujo; Gessica Wernke; Marcos Gomes Ghislandi; Alexandre Diório; Marcelo Fernandes Vieira; Rosângela Bergamasco; Maurício Alves da Motta Sobrinho; Alírio Egídio Rodrigues (Environmental Research, 2023)

Morphology of interommatidial sensilla of Discocephalini (Heteroptera: Pentatomidae: Discocephalinae) - Breno Batista Campos; André Oliveira Correia; Luiz Alexandre Campos; José Antônio Marin Fernandes (Arthropod Structure & Development, 2023)

Paleoenvironmental dynamics in central‐eastern Brazil during the last 23 000 years: tropical peatland record in the Cerrado biome - Camila Rodrigues Costa; Cynthia Fernandes Pinto da Luz; Ingrid Horák‐Terra; Plínio Barbosa de Camargo; Uidemar Morais Barral; Carlos Victor Mendonça‐Filho; Thamyres Sabrina Gonçalves; Alexandre Christófaro Silva (Journal of Quaternary Science, 2023)
The Cerrado biome is the second largest in Brazil, but the evolution of the Cerrado during the late Quaternary is not yet fully known. This study identifies paleoenvironmental changes during the last 23 000 years, based on a tropical mountain peatland record, in the Serra do Espinhaço Meridional in central‐eastern Brazil. A multi‐proxy approach was used that involved palynological analysis, stable isotopes (δ 13 C, δ 15 N), geochemistry, radiocarbon dating and multivariate statistics derived from a peatland core from Rio Preto (Minas Gerais state). The study reveals a very humid and cold climate during the late Pleistocene, with an increase in temperature and decrease in humidity at the Pleistocene–Holocene transition. During this period there was strong instability in the landscape (episodes of erosion). At the beginning of the Holocene there was a reduction in humidity with greater landscape stability. The current sub‐humid climatic conditions seem to have been established in the mid‐/late Holocene, with periods of landscape instability. Our findings agree with other Cerrado records that contradict previously established hypotheses, such as the Amazonian Refuge and the Pleistocene Arc.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Physicochemical characteristics and antimicrobial activity of Origanum vulgare L. essential oil and carvacrol on cariogenic bacteria: an in vitro and in silico study - Ellen Caroline Araújo da Silva; Letícia Lopes Leuthier; Alexandre Almeida Júnior; Jocianelle Maria Felix Fernandes Nunes; Fábio Correia Sampaio; Isabela Albuquerque Passos Farias (Natural Product Research, 2022)

Leptospira interrogans in bats in Rio Grande do Sul State, Brazil: epidemiologic aspects and phylogeny - Bruna Carolina Ulsenheimer; Ana Eucares von Laer; Alexandre Alberto Tonin; Aline Alves Scarpellini Campos; Helton Fernandes dos Santos; Luís Antônio Sangioni; Sônia de Avila Botton (Brazilian Journal of Microbiology, 2022)

Numerical Simulation of Embankment Construction on Soft Soil: A Case - Andréa Batista de Farias Dias; Thiago Augusto da Silva; Igor Fernandes Gomes; Silvio Romero de Melo Ferreira; Alexandre Duarte Gusmão; Jean Baptiste Joseph; Manoel Porfirio Cordão Neto (Geotechnical and Geological Engineering, 2022)

Does the same refuge signify the same reproductive tactics? Comparing the mating systems of two symbiont alpheid shrimps (Crustacea: Decapoda) - Rodrigo Guéron; Douglas Fernandes Rodrigues Alves; José Roberto Botelho de Souza; Alexandre Oliveira Almeida (Marine Ecology, 2022)
Animal populations can present different mating tactics according to the number of mates males or females obtain. The limiting factors for copulation in symbiont crustaceans are the size, structural complexity, and density of refuge, in addition to predation risk outside their shelters. In this study, we aimed to investigate, comparatively, if the occupation of the same refuge leads to the same reproductive tactic in two symbiont species of alpheid shrimps. For this purpose, we described the population distribution of Alpheus estuariensis , a burrowing shrimp, and Salmoneus carvachoi , a tenant species, in an intertidal mudflat in Pernambuco, northeastern Brazil. Alpheus estuariensis experiences sexual dimorphism relative to body and cheliped size, where males present larger body sizes and allocate more resources to cheliped growth than females. However, both males and females presented positive allometric growth in chelipeds. In S. carvachoi , male‐phase individuals reach smaller body sizes than hermaphrodites. Male‐phase shrimps experience positive allometry in cheliped size, while hermaphrodites do not. Both species were found inhabiting burrows as sexual pairs more frequently than expected by chance. Paired females of A. estuariensis were found carrying embryos more frequently than solitary ones. We did not find a statistical difference between the frequency of single and paired ovigerous hermaphrodites in S. carvachoi . Our results indicate that A. estuariensis is social monogamous, while S. carvachoi is promiscuous. We argue that different biological and ecological aspects of these species could explain the distinct tactics adopted by them. Alpheus estuariensis digs its own refuge and is a much larger species, bearing a more robust cheliped than S. carvachoi . Thus, we argue that the burrowing species ( A. estuariensis ) should monopolize and defend their refuge, and S. carvachoi only takes advantage of this resource.

A chloroacetamide derivative as a potent candidate for fusariosis treatment - Gabriella da Rosa Monte Machado; Stefânia Neiva Lavorato; William Lopes; Marilene Henning Vainstein; Mário Lettieri Teixeira; Ricardo José Alves; Saulo Fernandes de Andrade; Alexandre Meneghello Fuentefria (Brazilian Journal of Microbiology, 2022)

General biosafety measures for laboratory environments, outpatient clinics, medical centers, and veterinary hospitals during the SARS-CoV-2 pandemic - Bruna Carolina Ulsenheimer; Daniela Isabel Brayer Pereira; Helton Fernandes dos Santos; Ana Eucares von Laer; Alexandre Alberto Tonin; Mateus Matiuzzi da Costa; Luís Antonio Sangioni; Sônia de Avila Botton (Brazilian Journal of Microbiology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Sorbitan Monolaurate–Containing Liposomes Enhance Skin Cancer Cell Cytotoxicity and in Association with Microneedling Increase the Skin Penetration of 5-Fluorouracil - Luiziana Cavalcante Costa Fernandes Crisóstomo; Genuína Stephanie Guimarães Carvalho; Luzia Kalyne Almeida Moreira Leal; Tamara Gonçalves de Araújo; Karina Alexandre Barros Nogueira; Durcilene Alves da Silva; Fábio de Oliveira Silva Ribeiro; Raquel Petrilli; Josimar O. Eloy (AAPS PharmSciTech, 2022)

Antimicrobial activity of clioquinol and nitroxoline: a scoping review - Rachel Wykowski; Alexandre Meneghello Fuentefria; Saulo Fernandes de Andrade (Archives of Microbiology, 2022)

New record of the bat falcon (Falco rufigularis) in northeastern Brazil: Implications for its future distribution under climate change - Maria Eduarda Alves Ferreira; Rodrigo Ferraz Jardim Marques; Hélio Francisco Leite; Alexandre M. Fernandes (Biologia, 2022)

Integrated analysis reveals a new species of Corydoras Lacépède, 1803 (Siluriformes: Callichthyidae) in the lower Iguassu River, Brazil - Rafael Henrique da Rocha; Carlos Alexandre Fernandes; Thaís Souto Bignotto; Vladimir Pavan Margarido; Luiz Fernando Caserta Tencatt; Weferson Júnio da Graça; Éder André Gubiani (Organisms Diversity & Evolution, 2022)

A tubular ceramic membrane coated with TiO2-P25 for radial addition of H2O2 towards AMX removal from synthetic solutions and secondary urban wastewater - Alexandre Diório; Jennyfer Díaz-Angulo; Reynel M. Castellanos; Ana I. Gomes; Rosângela Bergamasco; Marcelo Fernandes Vieira; Márcia Dezotti; Miguel Angel Mueses; Fiderman Machuca-Martinez; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Importance of pneumatophore fringe-mudflat continuum for an estuary-dependent fish species - Juan Alves Pereira; Alexandre da Gama Fernandes Vieira Júnior; Éden Hávila Lima Guedes; Bianca de Freitas Terra; André Luiz Machado Pessanha (Marine Biology Research, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

Chronic exposure to lead acetate promotes changes in the alveolar bone of rats: microstructural and physical–chemical characterization - Lodinikki Lemoy Davis; Walessa Alana Bragança Aragão; Géssica de Oliveira Lopes; Luciana Guimaraes Eiró; Alexandre Rodrigues Freire; Felippe Bevilacqua Prado; Ana Cláudia Rossi; Allan da Silva Cruz; Kelly das Graças Fernandes Dantas; Alan Rodrigo Leal Albuquerque; Simone Patricia Aranha Paz; Rômulo Simões Angélica; et al. (Environmental Science and Pollution Research, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Synthesis, antibiotic modifying activity, ADMET study and molecular docking of chalcone (E)-3-(2,4-dichlorophenyl)-1-(2-hydroxyphenyl)prop-2-en-1-one in strains of Staphylococcus aureus carrying MepA efflux pumps - Janaína Esmeraldo Rocha; Thiago Sampaio de Freitas; Jayze da Cunha Xavier; Raimundo Luiz Silva Pereira; Francisco Nascimento Pereira; Carlos Emídio Sampaio Nogueira; Márcia Machado Marinho; Paulo Nogueira Bandeira; Maria Alyce Albuquerque Fernandes; Emmanuel Silva Marinho; Alexandre Magno Rodrigues Teixeira; Hélcio Silva dos Santos; et al. (Archives of Microbiology, 2022)

Effect of concentrate supplement to ewes on nutritive value of ingested Caatinga native forage nutritive value as affected by season - Wanderson Fiares de Carvalho; Arnaud Azevêdo Alves; Roberto Cláudio Fernandes Franco Pompeu; Alexandre Ribeiro Araújo; Francisco Éden Paiva Fernandes; Clésio dos Santos Costa; Delano de Sousa Oliveira; Humberto Queiroz Memória; Luciana Freitas Guedes; James Pierre Muir; Marcos Cláudio Pinheiro Rogério (Tropical Animal Health and Production, 2021)

Prediction of dry matter intake by meat sheep on tropical pastures - Antonio Leandro Chaves Gurgel; Gelson dos Santos Difante; João Virgínio Emerenciano Neto; Juliana Caroline Santos Santana; Patrick Bezerra Fernandes; Geraldo Tadeu dos Santos; Alexandre Menezes Dias; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Henrique Rocha de Medeiros (Tropical Animal Health and Production, 2021)

Reproductive and Stress Response Hormones of the Critically Endangered Southern Muriqui (Brachyteles arachnoides: Atelidae) Under Captive Conditions - Alexandre Bastos Fernandes Lima; Gisela Sobral; Gabriela Siqueira Martins; Alcides Pissinatti; Priscila Viau; Claudio Alvarenga de Oliveira (International Journal of Primatology, 2021)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Complete genome sequence and analysis of a Saccharomyces cerevisiae strain used for sugarcane spirit production - Ane Catarine Tosi Costa; Jacob Hornick; Tathiana Ferreira Sá Antunes; Alexandre Martins Costa Santos; A Alberto R. Fernandes; James R. Broach; Patricia M. B. Fernandes (Brazilian Journal of Microbiology, 2021)

Dietary nutrient restrictions in the post-weaning period change Santa Inês ewe lamb nutritional metabolic profile - Clésio dos Santos Costa; Marcos Cláudio Pinheiro Rogério; Alexandre Lima Ferreira; Fernanda Samarini Machado; Roberto Cláudio Fernandes Franco Pompeu; Francisco Gleyson da Silveira Alves; João Paulo Arcelino do Rêgo; Patrícia Guimarães Pimentel; James Pierre Muir; José Neuman Miranda Neiva (Tropical Animal Health and Production, 2021)

Occurrence and impact of fungicides residues on fermentation during wine production– A review - Angelo Gava; Cassandro Davi Emer; Evandro Ficagna; Saulo Fernandes de Andrade; Alexandre Meneghello Fuentefria (Food Additives & Contaminants: Part A, 2021)

A New Species of Liosphex Townes, 1977 (Hymenoptera: Rhopalosomatidae) from the Amazon Forest and New Records for the Genus in Brazil - Mayara Medeiros Bulbol; Alexandre Somavilla; Daniell Rodrigo Rodrigues Fernandes; Pedro Reck Bartholomay (Neotropical Entomology, 2021)

Nitrogen Stocks in Soil Classes Under Different Land Uses in the Brazilian Semiarid Region - Uemeson José dos Santos; Everardo Valadares de Sá Barretto Sampaio; Eunice Maia de Andrade; Alexandre de Siqueira Pinto; Bruno de Oliveira Dias; Kennedy Nascimento de Jesus; Mônica da Silva Santana; Tiago Diniz Althoff; Milton Marques Fernandes; Rômulo Simões Cezar Menezes (Journal of Soil Science and Plant Nutrition, 2021)

Water intake and ingestive behavior of sheep fed diets based on silages of cactus pear and tropical forages - Tiago Santos Silva; Gherman Garcia Leal de Araujo; Edson Mauro Santos; Juliana Silva de Oliveira; Fleming Sena Campos; Paulo Fernando Andrade Godoi; Glayciane Costa Gois; Alexandre Fernandes Perazzo; Ossival Lolato Ribeiro; Silvia Helena Nogueira Turco (Tropical Animal Health and Production, 2021)

Migration Deconvolution via Deep Learning - Manuel Ramón Vargas Avila; Luana Nobre Osorio; Júlio de Castro Vargas Fernandes; André Bulcão; Bruno Pereira-Dias; Bruno de Souza Silva; Pablo Machado Barros; Luiz Landau; Alexandre G. Evsukoff (Pure and Applied Geophysics, 2021)

Irradiance-driven 20-hydroxyecdysone production and morphophysiological changes in Pfaffia glomerata plants grown in vitro - Tatiane Dulcineia Silva; Diego Silva Batista; Kamila Motta Castro; Evandro Alexandre Fortini; Sérgio Heitor Sousa Felipe; Amanda Mendes Fernandes; Raysa Mayara Jesus Sousa; Kristhiano Chagas; José Victor Siqueira da Silva; Ludmila Nayara Freitas Correia; Gabriela Torres-Silva; Letícia Monteiro Farias; et al. (Protoplasma, 2021)

Trade‐offs between ontogenetic changes and food consumption in Brazilian silverside Atherinella brasiliensis from two tropical estuaries - Alexandre da Gama Fernandes Vieira Júnior; Diele Emele Pontes Carvalho de Lima; Natalice dos Santos Sales; Bianca de Freitas Terra; André Pessanha (Journal of Fish Biology, 2021)
Salinity variation in estuarine environments influences the distribution of fish species as well as the availability of food resources to be used by them. This study examines the effect of the range of salinity on the trade‐off between growth and feeding intensity of Atherinella brasiliensis from two tropical estuaries (positive and hypersaline). To investigate the effects of salinity, we hypothesized that hypersalinity negatively affects foraging intensity, consumption and prey selection by the Brazilian silverside, leading to differences in body condition . Sampling was carried out using the beach seine method in two areas of the estuaries (upper and lower zone) during rainy and dry periods. A total of 2549 stomachs (1124 for the positive estuary and 1425 for the hypersaline estuary) were examined, and the results indicated a dissimilarity of 92.7% of the diet between environments. In the positive estuary, there was more predation on Calanoida, Gastropoda, Hymenoptera, Ceratopogonidae larvae and Decapoda larvae, while Alga and plant‐material characterized the diet in the hypersaline estuary. Significant correlations between the volume of food and salinity were observed in both estuaries. The vacuity index indicated that hypersaline environments presented higher contributions of semifull stomachs, indicating an intense consumption of algae. On the other hand,in the positive estuary, these values were less intense, but the stomachs were always with animal items. The variation found for both environments reinforces the effect of salinity on the physiological mechanism of the populations once the higher proportions of filled stomachs in the hypersaline environment indicate the need for constant and high ingestion of prey to guarantee the pronounced energy expenditure with osmoregulation.

Quinolines derivatives as promising new antifungal candidates for the treatment of candidiasis and dermatophytosis - Gabriella da Rosa Monte Machado; Denise Diedrich; Thaís Carine Ruaro; Aline Rigon Zimmer; Mário Lettieri Teixeira; Luís Flávio de Oliveira; Mickael Jean; Pierre Van de Weghe; Saulo Fernandes de Andrade; Simone Cristina Baggio Gnoatto; Alexandre Meneghello Fuentefria (Brazilian Journal of Microbiology, 2020)

Functional and structural evaluation of the antileukaemic enzyme l-asparaginase II expressed at low temperature by different Escherichia coli strains - Werner Alfinito Feio de Moura; Leonardo Schultz; Carlos Alexandre Breyer; Ana Laura Pires de Oliveira; Carlos Abrunhosa Tairum; Gabriella Costa Fernandes; Marcos Hikari Toyama; Adalberto Pessoa-Jr; Gisele Monteiro; Marcos Antonio de Oliveira (Biotechnology Letters, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Biodiversity of caridean shrimps on rocky bottoms of two preserved islands on the southeastern Brazilian coast - Isabela R. R. Moraes; Alexandre Oliveira Almeida; Valter José Cobo; Douglas Fernandes Rodrigues Alves; Thiago Maia Davanso; Antonio Leão Castilho (Marine Biology Research, 2020)

A novel ZZ/ZW chromosome morphology type in Eigenmannia virescens (Gymnotiformes: Sternopygidae) from upper Paraná River basin - Carlos Alexandre Fernandes; Matheus Henrique Curiel; Leonardo Marcel Paiz; Lucas Baumgärtner; Diovani Piscor; Vladimir Pavan Margarido (Biologia, 2020)

Bacillus thuringiensis endotoxin production: a systematic review of the past 10 years - José Manoel W. Duarte Neto; Maria Carolina de A. Wanderley; Túlio Alexandre F. da Silva; Daniela A. Viana Marques; Gilvanda R. da Silva; Josimar Fernandes Gurgel; José de Paula Oliveira; Ana Lúcia F. Porto (World Journal of Microbiology and Biotechnology, 2020)

Rational selection of antifungal drugs to propose a new formulation strategy to control Candida biofilm formation on venous catheters - Paula Reginatto; Vanessa Zafanelli Bergamo; Simone Jacobus Berlitz; Irene Clemes Kulkamp Guerreiro; Saulo Fernandes de Andrade; Alexandre Meneghello Fuentefria (Brazilian Journal of Microbiology, 2020)

Heavy metal concentrations in Brazilian port areas and their relationships with microorganisms: can pollution in these areas change the microbial community? - Bruna Del Busso Zampieri; Vanessa da Costa Andrade; Roberta Merguizo Chinellato; Carlos Alexandre Borges Garcia; Marcos Antônio de Oliveira; Gunther Brucha; Ana Julia Fernandes Cardoso de Oliveira (Environmental Monitoring and Assessment, 2020)

Seroepidemiological study of Caseous lymphadenitis in sheep from the Northeast region of Brazil using an indirect ELISA - José Romero Alexandre Alves; Areano Ethério Moreira de Farias; Denize Monteiro dos Anjos; Ana Milena Cézar Lima; Patrícia Yoshida Faccioli-Martins; Carlos José Hoff de Souza; Raymundo Rizaldo Pinheiro; Francisco Selmo Fernandes Alves; Sérgio Santos de Azevedo; Clebert José Alves (Tropical Animal Health and Production, 2020)

Late Quaternary vegetation and climate dynamics in central‐eastern Brazil: insights from a ~35k cal a bp peat record in the Cerrado biome - Ingrid Horák‐Terra; Antonio Martínez Cortizas; Cynthia Fernandes Pinto Da Luz; Alexandre Christófaro Silva; Tim Mighall; Plínio Barbosa De Camargo; Carlos Victor Mendonça‐Filho; Paulo Eduardo De Oliveira; Francisco Willian Cruz; Pablo Vidal‐Torrado (Journal of Quaternary Science, 2020)
The late Quaternary evolution of central‐eastern Brazil has been under‐researched. Questions remain as to the origin of the Cerrado, a highly endangered biome, and other types of vegetation, such as the Capões – small vegetation islands of semi‐deciduous and mountain forests. We investigated the factors that influenced the expansion and contraction of the Cerrado and Capões during the late Quaternary (last ~35 ka), using a multi‐proxy approach: stable isotopes (δ 13 C, δ 15 N), geochemistry, pollen and multivariate statistics derived from a peat core (Pinheiro mire, Serra do Espinhaço Meridional). Five major shifts in precipitation, temperature, vegetation and landscape stability occurred at different timescales. Our study revealed that changes in the South Atlantic Convergence Zone (SACZ) seem to have been coeval with these shifts: from the Late Glacial Maximum to mid‐Holocene the SACZ remained near (~29.6 to ~16.5k cal a bp ) and over (~16.5 to ~6.1 k cal a bp ) the study area, providing humidity to the region. This challenges previous research which suggested that climate was drier for this time period. At present, the Capões are likely to be a remnant of a more humid climate; meanwhile, the Cerrado biome seems to have stablished in the late Holocene, after ~3.1 k cal a bp .

Humidity effects on avian blood parasites in the Caatinga of Brazil - Regina Carolina Ferreira de Souza Gomes; Bárbara Luiza Barbosa Teixeira; Cássia Lima Silva Gusmão; Alexandre M. Fernandes (Ornithology Research, 2020)

Mesquite pod meal as an additive increases milk total solids, lactose, fat and protein content in dairy cows - Luzyanne Varjão Aguiar; Herymá Giovane de Oliveira Silva; Sergio Augusto de Albuquerque Fernandes; Dirlane Novais Caires; Abias Santos Silva; Alexandre Etzberger Feistauer; Henrique Almeida da Silva; Lázaro Costa da Silva; Soraia Vanessa Matarazzo; Márcio dos Santos Pedreira (Tropical Animal Health and Production, 2020)

A multiplex RT-PCR method to detect papaya meleira virus complex in adult pre-flowering plants - Marlonni Maurastoni; Tathiana F. Sá-Antunes; Scarlett A. Oliveira; Alexandre M. C. Santos; José A. Ventura; Patricia M. B. Fernandes (Archives of Virology, 2020)

Concentration of Traces Metals in Underground Dams in the Semi-Arid of the Rio Grande do Norte State, Brazil: Case Study of the Sub-Basin of the Cobras River - Alexandre de Oliveira Lima; Nildo da Silva Dias; Cleyton dos Santos Fernandes; Francisco Pinheiro Lima Filho; Rene Chipana Rivera; Yago Leopoldo Eleuterio Gurgel de Sousa; Líssia Letícia de Paiva Oliveira; José Darcio Abrantes Sarmento; Hozano de Souza Lemos Neto (Water, Air, & Soil Pollution, 2020)

Water deficit modulates growth, morphology, and the essential oil profile in Lippia alba L. (Verbenaceae) grown in vitro - Kamila Motta de Castro; Diego Silva Batista; Tatiane Dulcineia Silva; Evandro Alexandre Fortini; Sérgio Heitor Sousa Felipe; Amanda Mendes Fernandes; Raysa Mayara de Jesus Sousa; Laís Stehling de Queiroz Nascimento; Victória Rabelo Campos; Richard Michael Grazul; Lyderson Facio Viccini; Wagner Campos Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

CRISPR, Prime Editing, Optogenetics, and DREADDs: New Therapeutic Approaches Provided by Emerging Technologies in the Treatment of Spinal Cord Injury - Vera Paschon; Felipe Fernandes Correia; Beatriz Cintra Morena; Victor Allisson da Silva; Gustavo Bispo dos Santos; Maria Cristina Carlan da Silva; Alexandre Fogaça Cristante; Stephanie Michelle Willerth; Florence Evelyne Perrin; Alexandre Hiroaki Kihara (Molecular Neurobiology, 2020)

Correction to: Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia Vieira; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2020)

Salinity modulates growth, morphology, and essential oil profile in Lippia alba L. (Verbenaceae) grown in vitro - Kamila Motta de Castro; Diego Silva Batista; Tatiane Dulcineia Silva; Evandro Alexandre Fortini; Sérgio Heitor Sousa Felipe; Amanda Mendes Fernandes; Raysa Mayara de Jesus Sousa; Laís Stehling de Queiroz Nascimento; Victória Rabelo Campos; Lyderson Facio Viccini; Richard Michael Grazul; Wagner Campos Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Chromosomal mapping of repetitive sequences in Hyphessobrycon eques (Characiformes, Characidae): a special case of the spreading of 5S rDNA clusters in a genome - Diovani Piscor; Leonardo Marcel Paiz; Lucas Baumgärtner; Fiorindo José Cerqueira; Carlos Alexandre Fernandes; Roberto Laridondo Lui; Patricia Pasquali Parise-Maltempi; Vladimir Pavan Margarido (Genetica, 2020)

The effects of climate change on the distribution of South American antbirds (Thamnophilus punctatus complex) as affected by niche divergences and contact zone interactions between species - Erasmo Andrade da Silva; Helder Farias Pereira de Araujo; Alexandre Aleixo; Alexandre Antonelli; Alexandre M. Fernandes (Journal of Ornithology, 2020)

DNA-based species identification of shark finning seizures in Southwest Atlantic: implications for wildlife trade surveillance and law enforcement - Bruno Lopes da Silva Ferrette; Rodrigo Rodrigues Domingues; Luis Henrique Fregadolli Ussami; Letícia Moraes; Carolina de Oliveira Magalhães; Alberto Ferreira de Amorim; Alexandre Wagner Silva Hilsdorf; Claudio Oliveira; Fausto Foresti; Fernando Fernandes Mendonça (Biodiversity and Conservation, 2019)

Photoperiod modulates growth, morphoanatomy, and linalool content in Lippia alba L. (Verbenaceae) cultured in vitro - Kamila Motta de Castro; Diego Silva Batista; Evandro Alexandre Fortini; Tatiane Dulcineia Silva; Sérgio Heitor Sousa Felipe; Amanda Mendes Fernandes; Raysa Mayara de Jesus Sousa; Laís Stehling de Queiroz Nascimento; Victória Rabelo Campos; Richard Michael Grazul; Lyderson Facio Viccini; Wagner Campos Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Seroepidemiological characterization and risk factors associated with seroconversion to Corynebacterium pseudotuberculosis in goats from Northeastern Brazil - Areano Ethério Moreira de Farias; José Romero Alexandre Alves; Francisco Selmo Fernandes Alves; Raymundo Rizaldo Pinheiro; Patrícia Yoshida Faccioli-Martins; Ana Milena César Lima; Sérgio Santos de Azevedo; Clebert José Alves (Tropical Animal Health and Production, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

REM sleep behavior disorder in patients with Parkinson’s disease: clinical and polysomnographic characteristics - Manoel Alves Sobreira-Neto; Márcio Alexandre Pena-Pereira; Emmanuelle Silva Tavares Sobreira; Marcos Hortes Nisihara Chagas; Carlos Maurício Oliveira de Almeida; Regina Maria França Fernandes; Vitor Tumas; Alan Luiz Eckeli (Sleep and Biological Rhythms, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Influence of storage time and nutrient medium on recovery of fibroblast-like cells from refrigerated collared peccary (Pecari tajacu Linnaeus, 1758) skin - Luiza Bento de Queiroz Neta; Gabriela Pereira de Oliveira Lira; Alana Azevedo Borges; Maria Valéria de Oliveira Santos; Maria Bárbara Silva; Lhara Ricarliany Medeiros de Oliveira; Alexandre Rodrigues Silva; Moacir Franco de Oliveira; Alexsandra Fernandes Pereira (In Vitro Cellular & Developmental Biology - Animal, 2018)

The Inventory of Geological Heritage of the State of São Paulo, Brazil: Methodological Basis, Results and Perspectives - Maria da Glória Motta Garcia; José Brilha; Flávia Fernanda de Lima; Jean Carlos Vargas; Annabel Pérez-Aguilar; Adriana Alves; Ginaldo Ademar da Cruz Campanha; Wânia Duleba; Frederico Meira Faleiros; Luiz Alberto Fernandes; Marisa de Souto Matos Fierz; Maria Judite Garcia; et al. (Geoheritage, 2018)

Deltamethrin-induced nuclear erythrocyte alteration and damage to the gills and liver of Colossoma macropomum - Fernanda dos Santos Cunha; Natalino da Costa Sousa; Rudã Fernandes Brandão Santos; Juliana Oliveira Meneses; Márcia Valéria Silva do Couto; Fabrício Tavares Cunha de Almeida; José Guedes de Sena Filho; Paulo César Falanghe Carneiro; Alexandre Nizio Maria; Rodrigo Yudi Fujimoto (Environmental Science and Pollution Research, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

Nucleolar organizer regions, 18S and 5S rDNA clusters in the chromosomes of Piabina argentea (Characiformes: Characidae) - Diovani Piscor; Carlos Alexandre Fernandes; Patricia Pasquali Parise-Maltempi (Biologia, 2017)

Distribution of Divo in Coffea genomes, a poorly described family of angiosperm LTR-Retrotransposons - Mathilde Dupeyron; Rogerio Fernandes de Souza; Perla Hamon; Alexandre de Kochko; Dominique Crouzillat; Emmanuel Couturon; Douglas Silva Domingues; Romain Guyot (Molecular Genetics and Genomics, 2017)

Tidal effects on phytoplankton assemblages in a near‐pristine estuary: a trait‐based approach for the case of a shallow tropical ecosystem in Brazil - Gleyci A. O. Moser; Fernanda Reinhardt Piedras; Anna Beatriz J. Oaquim; Daiana S. Souza; Suzana G. Leles; Domênica T. de Lima; Ana Beatriz A. Ramos; Cássia de O. Farias; Alexandre M. Fernandes (Marine Ecology, 2017)
The study of near‐pristine estuaries can be used as a tool for mitigation projects of harmful effects in anthropogenic eutrophic systems, since one can analyze the effect of temporal and spatial variations generated mainly by natural forces. Phytoplankton taxonomy has been used as a classical indicator to assess changes in transitional water communities, however alternative methods based on morphological, behavioral and physiological traits offer the opportunity to compare sites or moments with different taxonomic compositions. Our goal, in this context, is to evaluate phytoplankton community short‐term and seasonal variability in a near‐pristine estuary, Barra Grande estuary (Ilha Grande, RJ , Brazil), through species functional traits and thus community functional diversity. Samplings were carried out in a mooring in complete tidal cycles, seasonally during 2012. Our results showed a diverse phytoplankton community with 38 frequent and abundant taxa, marked by density variation (1.2 × 10.4–2 × 10.7 cell L −1 ) in depth, with abundance inversely related to tidal currents. The functional structure of the phytoplankton community measured by functional diversity ( FD ), varied seasonally in and across a gradient of tidal energy. A core community, mainly represented by flagellates and dinoflagellates, occurred in all observations and was highly functional (high FD ), exploiting a variety of habitats. The chain‐forming diatoms were associated with high tidal energy, and occurred in higher densities during summer. Phytoplankton cell size, cell shape, and the ability to form colonies are extremely plastic traits that can be regulated by the environment, however, isolated tychopelagic diatoms were present in the study area across all seasons, with higher contributions in autumn and winter, reflecting the shallow characteristic of this system. During the winter, an exposed sandbar was formed, and the lack of connection with the ocean resulted in an abundance of riverine and brackish water taxa. In this near‐pristine estuary the densities and occurrences of HAB phytoplankton are low. Trait‐based analyses add information about community structure, which can be impacted by anthropogenic actions in urbanized coastal systems. Thus the information provided by this study regarding phytoplankton functional diversity and its relation to nutrients and hydrography in Barra Grande Estuary can be applied as a baseline model for the development of public policies.

Chromosomal characteristics of rDNA in a conserved karyotype of two Sternopygus macrurus (Gymnotiformes: Sternopygidae) populations from upper Paraná River basin - Carlos Alexandre Fernandes; Lucas Baumgärtner; Leonardo Marcel Paiz; Vladimir Pavan Margarido; Ana Luiza de Brito Portela-Castro (Biologia, 2017)

Intake and ingestive behavior of lambs fed diets containing ammoniated buffel grass hay - Alexandre Fernandes Perazzo; Sansão de Paula Homem Neto; Ossival Lolato Ribeiro; Edson Mauro Santos; Gleidson Giordano Pinto de Carvalho; Juliana Silva de Oliveira; Higor Fábio Carvalho Bezerra; Fleming Sena Campos; José Esler de Freitas Junior (Tropical Animal Health and Production, 2017)

Inorganic and organic geochemical fingerprinting of sediment sources and ocean circulation on a complex continental margin (São Paulo Bight, Brazil) - Michel Michaelovitch de Mahiques; Till Jens Jörg Hanebuth; Renata Hanae Nagai; Marcia Caruso Bícego; Rubens Cesar Lopes Figueira; Silvia Helena Mello Sousa; Leticia Burone; Paula Franco-Fraguas; Satie Taniguchi; Alexandre Barbosa Salaroli; Gilberto Pereira Dias; Denise Menezes Prates; et al. (Ocean Science, 2017)
In this study, we use inorganic (metal) and organic (bulk and molecular) markers in sediment samples of the south-eastern Brazilian margin to investigate the response of geochemical fingerprints to the complex hydrodynamic processes present in the area. Results indicate the potential of export of terrigenous siliciclastic and organic constituents to the upper slope, even in an area with limited fluvial supply.Metal contents and especially the ln(Ti ∕ Al) and ln(Fe ∕ K) ratios make it possible to recognise the extension of shelf sediments toward the upper slope. Potassium, here expressed as ln(K ∕ Sc) and ln(K ∕ Al) ratios used as proxies of illite–kaolinite variations, proved to be an important parameter, especially because it allowed us to decipher the imprint of the northward flow of the Intermediate Western Boundary Current (IWBC) in comparison to the southward flows of the Brazil Current (BC) and Deep Western Boundary Current (DWBC). Using organic matter analyses, we were able to evaluate the extent of terrestrial contributions to the outer shelf and slope, even without the presence of significant fluvial input. In addition, molecular markers signify a slight increase in the input of C4-derived plants to the slope sediments, transported from distant areas by the main alongshore boundary currents, indicating that the terrestrial fraction of the organic matter deposited on the slope has a distinct origin when compared to shelf sediments.

First report of feline morbillivirus in South America - Gabriela Molinari Darold; Amauri Alcindo Alfieri; Lívia Saab Muraro; Alexandre Mendes Amude; Rosana Zanatta; Kelly Cristiane Ito Yamauchi; Alice Fernandes Alfieri; Michele Lunardi (Archives of Virology, 2017)

Chemical composition and anti-inflammatory activity of the leaves of Byrsonima verbascifolia - Aline Aparecida Saldanha; Lucas Fernandes do Carmo; Sara Batista do Nascimento; Natália Alves de Matos; Clarice de Carvalho Veloso; Ana Hortência Fonsêca Castro; Ric C. H. De Vos; André Klein; João Máximo de Siqueira; Carlos Alexandre Carollo; Thalita Vieira do Nascimento; Mônica Cristina Toffoli-Kadri; et al. (Journal of Natural Medicines, 2016)

Copper(II) complexes with naringenin and hesperetin: cytotoxic activity against A 549 human lung adenocarcinoma cells and investigation on the mode of action - Lenka V. Tamayo; Ligiane R. Gouvea; Anna C. Sousa; Ronniel M. Albuquerque; Sarah Fernandes Teixeira; Ricardo Alexandre de Azevedo; Sonia R. W. Louro; Adilson Kleber Ferreira; Heloisa Beraldo (BioMetals, 2016)

Thyroid hormones improve cardiac function and decrease expression of pro-apoptotic proteins in the heart of rats 14 days after infarction - Alexandre Luz de Castro; Rafael Oliveira Fernandes; Vanessa D. Ortiz; Cristina Campos; Jéssica H. P. Bonetto; Tânia R. G. Fernandes; Adriana Conzatti; Rafaela Siqueira; Angela Vicente Tavares; Paulo Cavalheiro Schenkel; Adriane Belló-Klein; Alex Sander da Rosa Araujo (Apoptosis, 2016)

NMDA Receptors and Oxidative Stress Induced by the Major Metabolites Accumulating in HMG Lyase Deficiency Mediate Hypophosphorylation of Cytoskeletal Proteins in Brain From Adolescent Rats: Potential Mechanisms Contributing to the Neuropathology of This Disease - Carolina Gonçalves Fernandes; Paula Pierozan; Gilberto Machado Soares; Fernanda Ferreira; Ângela Zanatta; Alexandre Umpierrez Amaral; Clarissa Günther Borges; Moacir Wajner; Regina Pessoa-Pureur (Neurotoxicity Research, 2015)

T3 and T4 decrease ROS levels and increase endothelial nitric oxide synthase expression in the myocardium of infarcted rats - Alexandre Luz de Castro; Angela Vicente Tavares; Rafael Oliveira Fernandes; Cristina Campos; Adriana Conzatti; Rafaela Siqueira; Tânia Regina G. Fernandes; Paulo Cavalheiro Schenkel; Carmem L. Sartório; Susana Llesuy; Adriane Belló-Klein; Alex Sander da Rosa Araujo (Molecular and Cellular Biochemistry, 2015)

Is the meiofauna a good indicator for climate change and anthropogenic impacts? - Daniela Zeppilli; Jozée Sarrazin; Daniel Leduc; Pedro Martinez Arbizu; Diego Fontaneto; Christophe Fontanier; Andrew J. Gooday; Reinhardt Møbjerg Kristensen; Viatcheslav N. Ivanenko; Martin V. Sørensen; Ann Vanreusel; Julien Thébault; et al. (Marine Biodiversity, 2015)

Exogenously induced brain activation regulates neuronal activity by top-down modulation: conceptualized model for electrical brain stimulation - Lauren Naomi Spezia Adachi; Alexandre Silva Quevedo; Andressa de Souza; Vanessa Leal Scarabelot; Joanna Ripoll Rozisky; Carla de Oliveira; Paulo Ricardo Marques Filho; Liciane Fernandes Medeiros; Felipe Fregni; Wolnei Caumo; Iraci L. S. Torres (Experimental Brain Research, 2015)

Modulation of apoptosis by sulforaphane is associated with PGC-1α stimulation and decreased oxidative stress in cardiac myoblasts - Rafael O. Fernandes; Jéssica H. P. Bonetto; Boran Baregzay; Alexandre L. de Castro; Stephanie Puukila; Heidi Forsyth; Paulo C. Schenkel; Susana F. Llesuy; Ilma Simoni Brum; Alex Sander R. Araujo; Neelam Khaper; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2015)

3-Indol carboxaldehyde, an imidazole synthesized from naphthoquinone β-lapachone downregulates Candida albicans biofilm - José Alexandre da Rocha Curvelo; Anna Lea Silva Barreto; Camila A. dos Anjos; Rafaela S. Santana; Ariadne Nunes Alonso; Maria Teresa Vilela Romanos; Kelly C. G. de Moura; Paula Fernandes Carneiro; Maristela Barbosa Portela; Maria do Carmo F. R. Pinto; Rosangela Maria de Araújo Soares (Medicinal Chemistry Research, 2015)

First isolation of Pseudogymnoascus destructans in bats from Portugal - Maria das Neves Paiva-Cardoso; Francisco Morinha; Paulo Barros; Hélia Vale-Gonçalves; Ana Cláudia Coelho; Lisete Fernandes; Paulo Travassos; Ana Sofia Faria; Estela Bastos; Mário Santos; João Alexandre Cabral (European Journal of Wildlife Research, 2014)

The effect of sex and genotype on growth performance, feed efficiency, and carcass traits of local sheep group Pantaneiro and Texel or Santa Inês crossbred finished on feedlot - Fernando Miranda de Vargas Junior; Charles Ferreira Martins; Guilherme dos Santos Pinto; Marcos Barbosa Ferreira; Hélio de Almeida Ricardo; André Gustavo Leão; Alexandre Rodrigo Mendes Fernandes; Alfredo Teixeira (Tropical Animal Health and Production, 2014)

Multiple speciation across the A ndes and throughout A mazonia: the case of the spot‐backed antbird species complex ( H ylophylax naevius / H ylophylax naevioides ) - Alexandre M. Fernandes; Michael Wink; Carla H. Sardelli; Alexandre Aleixo (Journal of Biogeography, 2014)
Aim To investigate the role of historical processes in the evolution of the spot‐backed antbird species complex Hylophylax naevius/Hylophylax naevioides (Aves, Thamnophilidae). Location Throughout the Amazon Basin and across the Andes in Central and northern South America. Methods We investigated the evolutionary history of the H. naevius / H. naevioides complex based on a total of 100 individuals from opposite banks of the major Amazonian rivers and both sides of the Andes. Nucleotide sequences from two mitochondrial DNA genes [1015 bp of cytochrome b (cyt b ) and 1023 bp of NADH dehydrogenase subunit 2 ( ND 2 )] and one nuclear marker [539 bp of intron 5 of the β‐fibrinogen ( BF 5 )] were obtained. Phylogenetic relationships were inferred using Bayesian and maximum likelihood methods. We used Bayesian coalescent‐based approaches to evaluate demographic changes through time, and to estimate the timing of the diversification events. Results Well‐supported allopatric and parapatric lineages were recovered within the H. naevius/H. naevioides complex, with high levels of genetic differentiation, both on opposite sides of rivers (0.6–7.1%) and across the Andes (6.9%). Molecular dating and population demography suggest cladogenesis in various periods, associated with distinct vicariance and dispersal events. Main conclusions Our data support the hypothesis that the uplift of the northern Andes and the consolidation of the modern Amazon drainage system were key to promoting the diversification of forest‐dwelling bird lineages in the northern Neotropics.

Phytoplankton spatial distribution on the Continental Shelf off Rio de Janeiro, from Paraíba do Sul River to Cabo Frio - Gleyci A. O. Moser; Robson Alves Takanohashi; Mariana de Chagas Braz; Domênica Teixeira de Lima; Fabiana Vasconcelos Kirsten; Josefa Varela Guerra; Alexandre M. Fernandes; Ricardo César Gonçalves Pollery (Hydrobiologia, 2014)

Development and validation of a set of standard area diagrams to estimate severity of potato early blight - Henrique Silva Silveira Duarte; Laércio Zambolim; Alexandre Sandri Capucho; Antonio Fernandes Nogueira Júnior; André Wilson Campos Rosado; Carine Rezende Cardoso; Pierce Anderson Paul; Eduardo Seiti Gomide Mizubuti (European Journal of Plant Pathology, 2013)

Fine-scale endemism of Amazonian birds in a threatened landscape - Alexandre M. Fernandes (Biodiversity and Conservation, 2013)

Tricellulin expression in brain endothelial and neural cells - Cibelle Mariano; Inês Palmela; Pedro Pereira; Adelaide Fernandes; Ana Sofia Falcão; Filipa Lourenço Cardoso; Ana Rita Vaz; Alexandre Rainha Campos; António Gonçalves-Ferreira; Kwang Sik Kim; Dora Brites; Maria Alexandra Brito (Cell and Tissue Research, 2013)

Phylogeography of the chestnut‐tailed antbird ( Myrmeciza hemimelaena ) clarifies the role of rivers in Amazonian biogeography - Alexandre M. Fernandes; Michael Wink; Alexandre Aleixo (Journal of Biogeography, 2012)
Aim We examined patterns of spatial and temporal diversification of the Amazonian endemic chestnut‐tailed antbird, Mymeciza hemimelaena (Thamnophilidae), to evaluate the diversification of a widespread avian taxon across rivers that potentially represent major natural barriers. Location Lowland Amazonia. Methods Sequences of the mitochondrial ND2 and cytochrome b genes were investigated from 65 individuals distributed throughout the entire range of M. hemimelaena , and including the two currently valid subspecies M. h. hemimelaena and M. h. pallens. Based on a combination of phylogeographic tools, molecular dating, and population genetic methods, we reconstructed a spatio‐temporal scenario of diversification of M. hemimelaena in the Amazon. Results The data revealed three genetically divergent and monophyletic groups in M. hemimelaena , which can also be distinguished by a combination of morphological and vocal characters. Two of these clades correspond to the previously described taxa M. h. hemimelaena and M. h. pallens , which are separated by the upper Madeira River, a main Amazonian tributary. The third clade is distributed between the middle reaches of the Madeira River and the much smaller tributaries Jiparaná and Aripuanã, and, although currently treated as M. h. pallens , clearly constitutes an independent evolutionary lineage probably deserving separate species status. Molecular clock and population genetic analyses indicate that diversification in this group occurred throughout the Pleistocene, with demographic fluctuations assumed for M. h. hemimelaena and M. h. pallens . Main conclusions The findings implicate rivers as barriers driving diversification in the M. hemimelaena complex. Levels of mitochondrial DNA divergence and associated morphological and vocal traits support its division into at least three separate species with comparatively small ranges. The existence of a previously unrecognized lineage in the M. hemimelaena complex, and the high degree of population structuring found in M. h. hemimelaena underscore the pervasiveness of cryptic endemism throughout Amazonia and the importance of DNA‐based taxonomic and phylogeographic studies in providing the accurate estimates of diversity that are essential for conservation planning.

Secondary metabolites isolated from Piper chimonantifolium and their antifungal activity - João Henrique G. Lago; Alexandre T. Ito; César M. Fernandes; Maria Claudia M. Young; Massuo J. Kato (Natural Product Research, 2012)

Chitooligosaccharides antagonize the cytotoxic effect of glucosamine - Cristiane Fernandes de Assis; Leandro Silva Costa; Raniere Fagundes Melo-Silveira; Ruth Medeiros Oliveira; Maria Giovana Binder Pagnoncelli; Hugo Alexandre Oliveira Rocha; Gorete Ribeiro de Macedo; Everaldo Silvino dos Santos (World Journal of Microbiology and Biotechnology, 2012)

Evidence that 2-methylacetoacetate induces oxidative stress in rat brain - Guilhian Leipnitz; Bianca Seminotti; Alexandre U. Amaral; Carolina G. Fernandes; Carlos S. Dutra-Filho; Moacir Wajner (Metabolic Brain Disease, 2010)

Influence of ketone bodies on oxidative stress parameters in brain of developing rats in vitro - Ana Paula Beskow; Carolina Gonçalves Fernandes; Guilhian Leipnitz; Lucila de Bortoli da Silva; Bianca Seminotti; Alexandre U. Amaral; Angela T. S. Wyse; Clóvis M. D. Wannmacher; Carmen R. Vargas; Carlos S. Dutra-Filho; Moacir Wajner (Metabolic Brain Disease, 2008)

Defense Proteins from Vigna Unguiculata Seed Exudates: Characterization and Inhibitory Activity Against Fusarium Oxysporum - Tatiana L. Rose; Alexandre da Silva Conceição; Jose Xavier-Filho; Lev A. Okorokov; Kátia V. S. Fernandes; Francis Marty; Danièle Marty-Mazars; André O. Carvalho; Valdirene M. Gomes (Plant and Soil, 2006)

A new Badnavirus species detected in Bougainvillea in Brazil - Eliana B. Rivas; Ligia M.L. Duarte; M. Amélia V. Alexandre; Flora M.C. Fernandes; Ricardo Harakava; César M. Chagas (Journal of General Plant Pathology, 2005)

Sympatric occurrence of three cytotypes and four morphological types of B chromosomes of Astyanax scabripinnis (Pisces, Characiformes) in the River Ivaí Basin, state of Paraná, Brazil - Carlos Alexandre Fernandes; Isabel Cristina Martins-Santos (Genetica, 2005)

Platelet-Activating Factor Modulates a Secreted Phosphatase Activity of the Trypanosomatid Parasite Herpetomonas muscarum muscarum - Patricia M.L. Dutra; Felipe A. Dias; Claudia O. Rodrigues; Alexandre Romeiro; Marcia Attias; Wanderley De Souza; Angela H.C.S. Lopes; José Roberto Meyer-Fernandes (Current Microbiology, 2001)